Active energy ray-curable composition
Patent Information
- Application Number
- JP2023561589
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-11-17
- Filing Date
- 2022-11-14
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2042-11-14
AI Technical Summary
【0010】 本発明によれば、特定の構造を有する(メタ)アクリレート(A)と、Aを除いた重合性化合物(B)を含有する活性エネルギー線硬化性組成物は、Aのバランス良い両親媒性と高い硬化性により、疎水性から親水性まで、単官能から多官能まで種々のBと良好な相溶性を示し、高い透明性と硬化性を有する。又(メタ)アクリレート(A)の分子内に環状置換基を有し、重合性化合物(B)として炭素数1~36の鎖状置換基を有する重合性化合物(b1)を含有することにより、A由来の環状置換基の間や周りにb1由来の鎖状置換基を充填や配置されやすくなり、活性エネルギー線硬化性組成物の硬化過程における体積の収縮を低めに抑えることができた。活性エネルギー線硬化性組成物が重合性化合物(B)として炭素数3~20の環状置換基を有する重合性化合物(b2)を含有する場合、(メタ)アクリレート(A)もb2も嵩高い環状置換基を有するため、硬化過程における体積の収縮が低く、得られる硬化物の透明性も耐熱性も優れる。更に、重合性化合物(b1)と重合性化合物(b2)を同時に含有することで、(メタ)アクリレート(A)とb2の環状置換基の立体的障害がb1の鎖状置換基により解消され、Aとb1およびb2を含有する活性エネルギー線硬化性組成物は、硬化性が高く、硬化収縮が低く、良好な相溶状態が保たれやすく、得られる硬化物の透明性、耐熱性と耐久性が良好ある。
Smart Images

Figure 0007618305000001 
Figure 0007618305000002 
Figure 0007618305000003
Abstract
Description
[Technical Field]
[0001] The present invention relates to an active energy ray-curable composition, a curable ink composition containing the same, a pressure-sensitive adhesive composition, an adhesive composition, a sealant composition, a paint composition, a nail cosmetic, a decorative coating agent, a dental material, and a cured product obtained by curing any of them. [Background technology]
[0002] Active energy ray-curable compositions generally consist of multiple polymerizable components and a photopolymerization initiator, and upon irradiation with active energy rays such as ultraviolet (UV) or electron beams (EB), they solidify (cure) from a liquid state at room temperature in a short time, and are used in a wide range of fields, including coating agents and paints, pressure-sensitive adhesives and adhesives, elastomer materials, materials for flexible displays, inkjet inks, sealing materials and sealants, dental hygiene materials, and optical materials. In particular, because they can be cured in any location or shape, they are increasingly being used in nail cosmetics such as gel nails and as materials for two-dimensional or three-dimensional stereolithography.
[0003] Active energy ray-curable compositions are required to have various performance characteristics depending on the field and environment in which they are used. To meet these requirements, a variety of polymerizable components must be combined. Generally, polymerizable oligomers (prepolymers) such as urethane acrylates and epoxy acrylates, polyfunctional monomers, monofunctional monomers, and photopolymerization initiators are blended as the main components. Depending on the application, additives such as fillers, pigments, dyes, leveling agents, viscosity modifiers, and polymerization inhibitors can be added. For example, Patent Document 1 describes an active energy ray-curable composition containing, as monofunctional monomers, a (meth)acrylate having an alicyclic skeleton, an N-substituted (meth)acrylamide, and a (meth)acrylate having a linear or branched alkyl group with 8 to 18 carbon atoms, as a polymerizable oligomer, a (meth)acrylate having a urethane group, and a photopolymerization initiator. It has been proposed that blending these components in a specific ratio can provide a cured product that exhibits both high elongation and high elastic modulus at high levels. The patent document discloses that monofunctional (meth)acrylates having an alicyclic skeleton and monofunctional (meth)acrylates having a linear or branched alkyl group with 8 to 18 carbon atoms are preferred from the viewpoint of elongation and modulus of elasticity of the cured product, that N-substituted (meth)acrylamides having an extremely short-chain alkyl group such as dimethyl or diethyl are preferred from the viewpoint of curability, and that urethane (meth)acrylates having one to two (meth)acryl groups are preferred from the viewpoint of elongation of the cured product. However, the patent document does not disclose the transparency of the curable composition or the transparency, heat resistance, impact resistance, durability, water resistance, etc. of the resulting cured product. Both (meth)acrylates having an alicyclic skeleton and (meth)acrylates having a linear or branched alkyl group with 8 to 18 carbon atoms are highly hydrophobic and have high steric hindrance, resulting in poor curability. On the other hand, N-substituted (meth)acrylamides having a short-chain alkyl group are known to be highly hydrophilic and curable. With such a combination of components, the curable composition and its cured product cannot be expected to exhibit good transparency, making them difficult to use in the optical field, such as optical components.Furthermore, due to differences in curing properties, the molecular-level structure of the resulting cured product becomes non-uniform, shrinkage during curing becomes large, and the resulting cured product is prone to internal stress and distortion, resulting in the problem of not being able to provide sufficient durability, impact resistance, and heat resistance for use in paints, pressure-sensitive adhesives, adhesives, electronic materials, dental materials, three-dimensional shaped objects, etc.
[0004] Patent Document 2 describes an active energy ray-curable resin composition containing a polycyclic carboxamide having a (meth)acryloyl group. The curable resin composition described in the patent document has good UV curability, and the obtained cured film has good surface hardness as a hard coat. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent Publication No. 2021-123720 [Patent Document 2] Japanese Patent Application Publication No. 2018-95626 Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present invention is to provide a novel active energy ray-curable composition that has a wide variety of properties required of an active energy ray-curable composition, and in particular is able to simultaneously achieve high transparency, high curability against LED light, and resistance to cure shrinkage, which have conventionally been difficult to achieve simultaneously.
[0007] Another object of the present invention is to provide a cured product of an active energy ray-curable composition that has a wide variety of properties required of the cured product, and in particular, that can simultaneously achieve transparency, heat resistance, impact resistance, water resistance, durability, and impact resistance, which have conventionally been difficult to achieve simultaneously. [Means for solving the problem]
[0008] As a result of extensive research, the present inventors have found that the above-mentioned problems can be solved by an active energy ray-curable composition comprising a (meth)acrylate (A) having an amide group and a cyclic substituent in the molecule, and a polymerizable compound (B) (excluding A) having one or more ethylenically unsaturated groups in the molecule, wherein the polymerizable compound (B) is a polymerizable compound (b1) having a chain substituent having at least 1 to 36 carbon atoms and / or a polymerizable compound (b2) having a cyclic substituent having 3 to 20 carbon atoms, and thus have completed the present invention.
[0009] That is, the present invention is based on the following constitution. (1) a (meth)acrylate (A) having an amide group and a cyclic substituent in the molecule; An active energy ray-curable composition containing a polymerizable compound (B) (excluding A) having one or more ethylenically unsaturated groups in the molecule, The polymerizable compound (B) is an active energy ray-curable composition containing a polymerizable compound (b1) having a chain substituent having 1 to 36 carbon atoms and / or a polymerizable compound (b2) having a cyclic substituent having 3 to 20 carbon atoms. (2) The active energy ray-curable composition according to (1) above, wherein the (meth)acrylate (A) has, as a cyclic substituent, one or more substituents selected from a saturated or unsaturated polycyclic aliphatic ring, a monocyclic or polycyclic aromatic ring, a saturated or unsaturated aliphatic heterocycle, and an aromatic heterocycle. (3) The active energy ray-curable composition according to (1) or (2), wherein the (meth)acrylate (A) has an amide group between the (meth)acrylate group and the cyclic substituent. (4) The active energy ray-curable composition according to any one of (1) to (3), wherein the polymerizable compound (B) has, as the ethylenically unsaturated group, one or more groups selected from a (meth)acrylamide group, a (meth)acrylate group, a vinyl group, a vinyl ether group, an alkyl vinyl ether group, an allyl group, a (meth)allyl ether group, and a maleimide group. (5) The active energy ray-curable composition according to any one of (1) to (4), wherein the content of the (meth)acrylate (A) is 0.1 to 99.5 mass%, the content of the polymerizable compound (b1) is 0.3 to 80 mass%, and the content of the polymerizable compound (b2) is 0.2 to 70 mass%, based on the total amount of the active energy ray-curable composition. (6) The active energy ray-curable composition according to any one of (1) to (5), which has a cure shrinkage rate of 5% or less. (7) The active energy ray-curable composition according to any one of (1) to (6), wherein the saturated water absorption of the cured product of the active energy ray-curable composition is 10% or less. (8) An ink composition containing the actinic ray-curable composition according to any one of (1) to (7). (9) An ink composition for two-dimensional or three-dimensional modeling, comprising the active energy ray-curable composition according to any one of (1) to (7) above. (10) A pressure-sensitive adhesive composition containing the active energy ray-curable composition according to any one of (1) to (7). (11) An adhesive composition containing the active energy ray-curable composition according to any one of (1) to (7). (12) A coating composition containing the active energy ray-curable composition according to any one of (1) to (7) above. (13) A sealant composition containing the active energy ray-curable composition according to any one of (1) to (7) above. (14) A nail cosmetic containing the active energy ray-curable composition according to any one of (1) to (7) above. (15) A decorative coating agent containing the active energy ray-curable composition according to any one of (1) to (7) above. (16) A dental material containing the active energy ray-curable composition according to any one of (1) to (7). [Effects of the Invention]
[0010] According to the present invention, an active energy ray-curable composition containing a (meth)acrylate (A) having a specific structure and a polymerizable compound (B) excluding A exhibits good compatibility with various Bs, ranging from hydrophobic to hydrophilic and from monofunctional to polyfunctional, due to the well-balanced amphiphilicity and high curability of A, resulting in high transparency and curability. Furthermore, by including a polymerizable compound (b1) having a cyclic substituent within the (meth)acrylate (A) molecule and a chain-like substituent having 1 to 36 carbon atoms as the polymerizable compound (B), the chain-like substituent derived from b1 can be easily filled or arranged between or around the cyclic substituent derived from A, thereby minimizing volumetric shrinkage during the curing process of the active energy ray-curable composition. When the active energy ray-curable composition contains a polymerizable compound (b2) having a cyclic substituent having 3 to 20 carbon atoms as the polymerizable compound (B), both the (meth)acrylate (A) and b2 have bulky cyclic substituents, resulting in low volumetric shrinkage during the curing process and excellent transparency and heat resistance of the resulting cured product. Furthermore, by simultaneously containing the polymerizable compound (b1) and the polymerizable compound (b2), the steric hindrance of the cyclic substituent of the (meth)acrylate (A) and b2 is eliminated by the chain substituent of b1, and the active energy ray-curable composition containing A, b1, and b2 has high curability, low cure shrinkage, and is easily able to maintain a good compatibility state, and the obtained cured product has good transparency, heat resistance, and durability.
[0011] The (meth)acrylate (A) has a cyclic substituent in the molecule and has a high refractive index. Due to the interaction between the cyclic substituent and the amide group in the molecule, the glass transition temperature (Tg) of a homopolymer of the (meth)acrylate (A) is higher than that of a typical cyclic polymer. A cured product obtained from an active energy ray-curable composition containing a (meth)acrylate (A) of such a specific structure and a polymerizable compound (B) has high transparency, heat resistance, durability, and impact resistance. Furthermore, due to the unique effect of the interaction between the amide group in the (meth)acrylate (A) and the cyclic substituent, the cured product obtained from the active energy ray-curable composition of the present invention exhibits high yellowing resistance and water resistance, despite the presence of an amide group that is generally recognized as being prone to coloration and having poor water resistance. When the (meth)acrylate (A) has an unsaturated polycyclic aliphatic ring and / or an unsaturated aliphatic heterocycle, the unsaturated bonds in the ring undergo a partial polymerization reaction upon irradiation with active energy rays, and A becomes a special monomer between monofunctional and polyfunctional, resulting in a cured product with excellent impact resistance.
[0012] The active energy ray-curable composition of the present invention exhibits high curability against both the light (wavelength range 250 to 450 nm) of a general-purpose UV ink-curing metal halide lamp and the light (wavelengths 365 nm, 385 nm, 395 nm, and 405 nm) of a highly safe LED. The liquid viscosity of the curable composition can be adjusted almost without limit from low to high depending on the application. The composition can be provided as a curable ink composition for printing, such as inkjet printing, screen printing, offset printing, and flexographic printing, or as a curable ink composition for two-dimensional or three-dimensional modeling. The active energy ray-curable composition of the present invention also exhibits high wettability and adhesion to a variety of substrates, from low-polarity plastics to high-polarity glass and metals, and can be provided as a curable pressure-sensitive adhesive composition, adhesive composition, paint composition, sealant composition, nail cosmetics, decorative coating agents used in decorative films and sheets, dental materials, and the like. Furthermore, when the (meth)acrylate (A) has an unsaturated polycyclic aliphatic ring and / or an unsaturated aliphatic heterocycle, the (meth)acrylate group can be polymerized by photopolymerization, and then these unsaturated groups can be polymerized by thermal polymerization, and the active energy ray-curable composition of the present invention can be suitably used for bonding opaque materials such as metals, bonding different materials, etc. DETAILED DESCRIPTION OF THE INVENTION
[0013] Hereinafter, embodiments of the present invention will be described in detail. First to fifth embodiments of the present invention (hereinafter collectively referred to as the present embodiments) are active energy ray-curable compositions (E). The active energy ray-curable compositions (E) according to the present embodiments (hereinafter also simply referred to as "curable compositions (E)") contain a (meth)acrylate (A) having an amide group and a cyclic substituent in the molecule, and a polymerizable compound (B) (excluding A) having one or more ethylenically unsaturated groups in the molecule, and contain a polymerizable compound (b1) having a chain substituent having 1 to 36 carbon atoms and / or a polymerizable compound (b2) having a cyclic substituent having 3 to 20 carbon atoms as B.
[0014] By including the (meth)acrylate (A), the active energy ray-curable composition (E) has high curability while suppressing cure shrinkage during curing of E. The interaction between A and B improves the transparency of E, further reducing cure shrinkage of E, and the cured product of E has high yellowing resistance and water resistance. Furthermore, by including A and the aforementioned b2, E has high heat resistance and durability.
[0015] Based on the total mass of the active energy ray-curable composition (E), the content of the (meth)acrylate (A) is preferably 0.1 to 99.5 mass%, the content of the polymerizable compound (b1) is preferably 0.3 to 80 mass%, and the content of the polymerizable compound (b2) is preferably 0.2 to 70 mass%, and the sum of the contents of b1 and b2 is more preferably 0.5 mass% or more. When the contents of A, b1, and b2 are within these ranges, the transparency, curability, and cure shrinkage resistance of E can be simultaneously achieved, and the resulting cured product can simultaneously achieve transparency, heat resistance, yellowing resistance, durability, and water resistance. Furthermore, from the viewpoint of simultaneously achieving the above-mentioned various properties and high performance in E and its cured product, the content of A is more preferably 1 to 95 mass%, the content of b1 is 5 to 70 mass%, and the content of b2 is 2 to 60 mass%, and it is particularly preferably 5 to 90 mass%, the content of b1 is 10 to 60 mass%, and the content of b2 is 5 to 50 mass%.
[0016] The (meth)acrylate (A) having an amide group and a cyclic substituent in the molecule is not particularly limited as long as it is a compound having one or more amide groups and one or more cyclic substituents in the molecule, and one or more methacrylate groups and / or acrylate groups. The cyclic substituent is one or more substituents selected from monocyclic or polycyclic aliphatic rings, monocyclic or polycyclic aromatic rings, aliphatic heterocycles, and aromatic heterocycles, and these substituents may be saturated or unsaturated rings, such as cyclohexyl, dicyclopentanyl, dicyclopentenyl, bornyl, isobornyl, adamantyl, norbornane, norbornene, oxanorbornane, oxanorbornene, azanorbornane, azanorbornene, tricyclodecane, phenyl, naphthalene, triphenylene, pyrene, perylene, indacene, biphenylene, acenaphthylene, phenalene, anthracene, cyclohexylphenyl, 4-morpholinophenyl, various bisphenol groups, and bisoxazoline groups. Only one type of these cyclic substituents may be present, or two or more types may be present.
[0017] The (meth)acrylate (A) may further have a substituent (R) on its cyclic substituent. The substituent R is a linear alkyl group or hydroxyalkylene group having 1 to 6 carbon atoms, optionally substituted with an ethylenically unsaturated bond, an alkenyl group or alkyleneoxyalkyl group having 2 to 6 carbon atoms, or a branched alkyl group having 3 to 6 carbon atoms. The ethylenically unsaturated group in R is one or more groups selected from the group consisting of a (meth)acrylate group, a (meth)acrylamide group, a vinyl group, a vinyl ether group, an alkyl vinyl ether group, an allyl group, a (meth)allyl ether group, and a maleimide group. The cyclic substituent of A may be a saturated or unsaturated ring. It is preferred that the cyclic substituent of A is an unsaturated ring and / or that the substituent R has an ethylenically unsaturated group. In this preferred case, A has two or more unsaturated groups in the molecule, which enhances the curability of the active energy ray-curable composition (E) and further improves the heat resistance, durability, water resistance, etc. of the resulting cured product. Furthermore, it is more preferable that the unsaturated group of the unsaturated ring of A and / or the ethylenically unsaturated group of the substituent R are groups other than (meth)methacrylate groups. In this more preferable case, A has two or more unsaturated groups with different structures in the molecule, and by adjusting the type and intensity of the active energy ray, the two or more different unsaturated groups can be cured in sequence, making it possible to gradually increase the crosslinking rate of the cured product while suppressing the cure shrinkage rate, and to obtain a cured product with excellent impact resistance.
[0018] Examples of the amide group of the (meth)acrylate (A) include a secondary amide group (N-substituted amide), a tertiary amide group (N,N-disubstituted amide), a diacetamide group, and an N-substituted diacetamide group. It is preferable that A has the amide group between the (meth)acrylate group and the cyclic substituent. In this case, the effect of the interaction between the amide group and the (meth)acrylate group and / or the interaction between the amide group and the cyclic substituent can be more efficiently exhibited compared to when these groups act alone. It is preferable that A has the (meth)acrylate group and the amide group linked by a linear or branched alkylene group having 1 to 6 carbon atoms (first linking group), and the amide group and the cyclic substituent linked directly or via a linear or branched alkylene group having 1 to 6 carbon atoms (second linking group). Furthermore, when the (meth)acrylate group and the amide group are linked via a linear alkylene group having 2 to 4 carbon atoms and the amide group is directly linked to the cyclic substituent, the curability of the (meth)acrylate group against active energy rays is improved and yellowing of the cured product over time due to the amide group is reduced, which is more preferable. Furthermore, when the cyclic substituent is an unsaturated ring, the curability against active energy rays is further improved, which is particularly preferable.
[0019] The (meth)acrylate (A) can be synthesized by a known method. Generally, examples of the method include a method in which a carboxylic acid, carboxylic acid ester, carboxylic acid chloride, or carboxylic acid anhydride having a cyclic substituent is subjected to an amidation reaction with a compound having a hydroxy group and an amino group, such as an alkanolamine, to give a carboxamide compound having a hydroxy group and a cyclic substituent, and then the compound is subjected to an esterification reaction with (meth)acrylic anhydride or (meth)acrylic acid, or a transesterification reaction with a lower alkyl (meth)acrylic acid ester; and a method in which an N-substituted amide or N,N-disubstituted amide substituted with a cyclic substituent having a hydroxy group is subjected to an esterification reaction with (meth)acrylic anhydride or (meth)acrylic acid, or a transesterification reaction with a lower alkyl (meth)acrylic acid ester.
[0020] The (meth)acrylate (A) is a (meth)acryloyloxyalkylene norbornane carboxamide such as (meth)acryloyloxymethylene norbornane carboxamide, (meth)acryloyloxyethylene norbornane carboxamide, (meth)acryloyloxy(iso)propylene norbornane carboxamide, (meth)acryloyloxy(iso)butylene norbornane carboxamide, (meth)acryloyloxy(iso)amylene norbornane carboxamide, or (meth)acryloyloxy(iso)hexylene norbornane carboxamide, (meth)acryloyloxymethylene bornene carboxamide, (meth)acryloyloxyethylene norbornane carboxamide, (meth)acryloyloxy(iso)propylene norbornane carboxamide, (meth)acryloyloxy (meth)acryloyloxyalkylenenorbornenecarboxamides such as (meth)acryloyloxy(iso)butylenenorbornenecarboxamide, (meth)acryloyloxy(iso)amylenenorbornenecarboxamide, and (meth)acryloyloxy(iso)hexylenenorbornenecarboxamide; (meth)acryloyloxymethyleneoxanorbornanecarboxamide; (meth)acryloyloxyethyleneoxanorbornanecarboxamide; and (meth)acryloyloxy(iso)propyleneoxanorbornanecarboxamide. (meth)acryloyloxyalkylene oxanorbornane carboxamides such as (meth)acryloyloxy(iso)butylene oxanorbornane carboxamide, (meth)acryloyloxy(iso)amylene oxanorbornane carboxamide, and (meth)acryloyloxy(iso)hexylene oxanorbornane carboxamide; (meth)acryloyloxymethylene oxanorbornene carboxamide; (meth)acryloyloxyethylene oxanorbornene carboxamide; and (meth)acryloyloxy(iso)propylene oxanorbornene carboxamide.(meth)acryloyloxyalkylene oxanorbornene carboxamides such as (meth)acryloyloxy(iso)butylene oxanorbornene carboxamide, (meth)acryloyloxy(iso)amylene oxanorbornene carboxamide, and (meth)acryloyloxy(iso)hexylene oxanorbornene carboxamide, (meth)acryloyloxyalkylene (carbon number 1 to 6) norbornene-2-alkyl (carbon number 1 to 6)-2-carboxamides, (meth)acryloyloxyalkylene (carbon number 1 to 6) dicyclopentenyl carboxamide, (meth)acryloyloxyalkylene (carbon number 1 to 6) dicyclopentanyl carboxamide, (meth)acryloyloxyalkylene (carbon number 1 to 6), alkyl (carbon number 1 to 6), Examples thereof include dicyclopentanyl dicarboxamide, bis(meth)acryloyloxyalkylene (carbon number 1 to 6) dicyclopentanyl dicarboxamide, (meth)acryloyloxyalkylene (carbon number 1 to 6) isobornane carboxamide, and bis(meth)acryloyloxyalkylene (carbon number 1 to 6) cyclohexane dicarboxamide.
[0021] The polymerizable compound (B), excluding the (meth)acrylate (A), is a compound having one or more ethylenically unsaturated groups in the molecule. The ethylenically unsaturated groups of B are one or more groups selected from the group consisting of (meth)acrylate groups, (meth)acrylamide groups, vinyl groups, vinyl ether groups, alkyl vinyl ether groups, allyl groups, (meth)allyl ether groups, and maleimide groups, and are preferably acrylamide groups and acrylate groups from the viewpoint of high curability against active energy rays. B contains a polymerizable compound (b1) having a chain substituent having 1 to 36 carbon atoms and / or a polymerizable compound (b2) having a cyclic substituent having 3 to 20 carbon atoms (excluding A and b1), and both b1 and b2 contain a monofunctional polymerizable compound having one ethylenically unsaturated group in the molecule (hereinafter also referred to as a monofunctional monomer) and a polyfunctional polymerizable compound having two or more ethylenically unsaturated groups in the molecule (hereinafter also referred to as a polyfunctional monomer), and, excluding b1 and b2, may also contain a polymerizable compound (b3) having one or more ethylenically unsaturated groups in the molecule.
[0022] The active energy ray-curable composition (E) according to this embodiment contains a polymerizable compound (b1) or a polymerizable compound (b2), and preferably contains both b1 and b2 from the viewpoint of further improving various physical properties. By containing b1 and b2, E can be optimized for various applications, such as viscosity, pigment dispersibility, printability, etc. of an inkjet ink composition, modeling accuracy, strength of a modeled object, etc. of a curable composition for three-dimensional stereolithography, adhesion, reworkability, yellowing resistance, etc. of a pressure-sensitive adhesive composition, adhesive strength, impact resistance, etc. of an adhesive composition, wettability to a substrate, and surface hardness of a coating composition. From this viewpoint, the mass ratio of the content of b1 to b2 is more preferably 30 / 1 to 1 / 10, and particularly preferably 10 / 1 to 1 / 5.
[0023] The polymerizable compound (b1) has one or more ethylenically unsaturated groups and a chain-like substituent having 1 to 36 carbon atoms in the molecule, and the chain-like substituent may be linear or branched, and may be a saturated alkyl group or an unsaturated alkenyl group, and may have or be substituted with a hydroxyl group, a primary amino group, a secondary amino group, a tertiary amino group, a thiol group, an ether group, an ester group, a ketone group, a carboxylic acid group, an amide group, a sulfonic acid group, etc. The ethylenically unsaturated group contained in b1 is one or more ethylenically unsaturated groups selected from the group consisting of a (meth)acrylate group, a (meth)acrylamide group, a vinyl group, a vinyl ether group, an alkyl vinyl ether group, an allyl group, a (meth)allyl ether group, and a maleimide group, and from the viewpoint of high curability against active energy rays, an acrylamide group and an acrylate group are preferred.
[0024] In the above b1, examples of the monofunctional polymerizable compound having an acrylamide group include linear or branched N-substituted alkylacrylamides having 1 to 36 carbon atoms, N,N-disubstituted dialkylacrylamides, linear or branched N-substituted alkenylacrylamides having 1 to 36 carbon atoms, linear or branched N,N-disubstituted dialkenylacrylamides having 1 to 36 carbon atoms, linear or branched N,N-disubstituted alkylalkenylacrylamides having 1 to 36 carbon atoms; linear or branched N,N-disubstituted alkylalkenylacrylamides having 1 to 36 carbon atoms; Examples of such alkyl acrylamides include linear or branched N-substituted alkylacrylamides having 1 to 36 carbon atoms, N,N-disubstituted dialkylacrylamides, linear or branched N-substituted alkenyl acrylamides having 1 to 36 carbon atoms, linear or branched N,N-disubstituted dialkenyl acrylamides having 1 to 36 carbon atoms, and linear or branched N,N-disubstituted alkylalkenyl acrylamides having 1 to 36 carbon atoms, which have or are substituted with an alkyl group, ether group, ester group, ketone group, carboxylic acid group, amide group, sulfonic acid group, or the like. Among these, dimethylacrylamide, diethylacrylamide, isopropylacrylamide, t-butylacrylamide, ethylhexylacrylamide, n-octylacrylamide, t-octylacrylamide, oleylacrylamide, methoxybutylacrylamide, butoxymethylacrylamide, N-(2-hydroxyethyl)acrylamide, N-(2-hydroxypropyl)acrylamide, N-[3-(dimethylamino)]propylacrylamide, and diacetoneacrylamide are preferred from the viewpoint of easy availability of industrial products, etc. These monofunctional polymerizable compounds having an acrylamide group may be used alone or in combination of two or more.
[0025] Examples of the polyfunctional polymerizable compound having an acrylamide group in b1 include monomer-type polyfunctional polymerizable compounds having an acrylamide group, such as methylene bis(meth)acrylamide, ethylene bis(meth)acrylamide, diallyl (meth)acrylamide, N-[tris(3-(meth)acrylamidopropoxymethyl)methyl](meth)acrylamide, N,N-bis(2-(meth)acrylamidoethyl)(meth)acrylamide, 4,7,10-trioxa-1,13-tridecane bis(meth)acrylamide, and N,N'-1,2-ethanedyl bis[N-(2-(meth)acrylamidoethyl)](meth)acrylamide, and oligomer-type polyfunctional polymerizable compounds having an acrylamide group, such as polyurethane diacrylamide having no cyclic substituent. These polyfunctional polymerizable compounds having an acrylamide group may be used alone or in combination of two or more.
[0026] In the above b1, examples of the monofunctional polymerizable compound having an acrylate group include linear or branched alkyl acrylates having 1 to 36 carbon atoms, linear or branched alkenyl acrylates having 1 to 36 carbon atoms, linear or branched alkyl acrylates having 1 to 36 carbon atoms, and linear or branched alkenyl acrylates having 1 to 36 carbon atoms, each of which has or is substituted with one or more hydroxy groups, primary to tertiary amino groups, thiol groups, ether groups, ester groups, ketone groups, carboxylic acid groups, amide groups, sulfonic acid groups, etc. Among these, from the viewpoint of easy availability of industrial products, examples include butyl acrylate, 2-ethylhexyl acrylate, stearyl acrylate, 2-(2-ethoxyethoxy)ethyl acrylate, hydroxyethyl acrylate, and 4-hydroxybutyl acrylate.
[0027] Examples of the polyfunctional polymerizable compound having an acrylate group in b1 include ethylene glycol diacrylate, diethylene glycol diacrylate, methoxydipropylene glycol acrylate, methoxytripropylene glycol acrylate, 1,4-butanediol diacrylate, 1,6-hexanediol diacrylate, 1,6-hexanediol ethylene oxide-modified diacrylate, hydroxypivalic acid neopentyl glycol diacrylate, glycerin diacrylate, pentaerythritol tetraacrylate, pentaerythritol triacrylate, pentaerythritol diacrylate, dipentaerythritol triacrylate, and dipentaerythritol hemiacrylate. Examples of suitable polyfunctional polymerizable compounds include monomer-type polyfunctional polymerizable compounds having an acrylate group, such as ethylene glycol diglycidyl ether diacrylate, diethylene glycol diglycidyl ether diacrylate, trimethylolethane triacrylate, and trimethylolpropane triacrylate, and oligomer-type polyfunctional polymerizable compounds having an acrylate group, such as polyether diacrylates, such as polyethylene glycol diacrylate, polypropylene glycol diacrylate, and polytetramethylene glycol diacrylate, polyurethane diacrylate, and polyester diacrylate. These polyfunctional polymerizable compounds having an acrylate group may be used alone or in combination of two or more.
[0028] The polymerizable compound (b2) has one or more ethylenically unsaturated groups and cyclic substituents having 3 to 20 carbon atoms in the molecule, and the cyclic substituents are one or more substituents selected from monocyclic or polycyclic aliphatic rings, aromatic rings, aliphatic heterocycles, and monocyclic or polycyclic aromatic heterocycles. The aliphatic rings and aliphatic heterocycles may be saturated or unsaturated rings. The ethylenically unsaturated groups in b2 are one or more ethylenically unsaturated groups selected from the group consisting of (meth)acrylate groups, (meth)acrylamide groups, vinyl groups, vinyl ether groups, alkyl vinyl ether groups, allyl groups, (meth)allyl ether groups, and maleimide groups. From the viewpoint of high curability against active energy rays, acrylamide groups and acrylate groups are preferred. When the ethylenically unsaturated groups in b2 are (meth)acrylate groups, the molecule does not contain amide groups. When the ethylenically unsaturated group that b2 has is a (meth)acrylamide group, the molecule does not have a (meth)acrylate group.
[0029] In the above b2, examples of the monofunctional polymerizable compound having an acrylamide group include N-cyclohexyl acrylamide, N,N-dicyclohexyl acrylamide, N-cyclohexyl-N-methyl acrylamide, N-cyclohexyl-N-ethyl acrylamide, N-cyclohexyl-N-propyl acrylamide, N-cyclohexyl-N-butyl acrylamide, N-phenyl acrylamide, N-acryloyl morpholine, N-acryloyl piperidine, N-acryloyl-2-methyl piperidine, N-acryloyl methyl acrylate ... N-acryloyl-3-methylpiperidine, N-acryloyl-4-methylpiperidine, N-acryloyl-2,6-dimethylpiperidine, N-acryloyl-3,5-dimethylpiperidine, N-acryloyl-3,3-dimethylpiperidine, N-acryloyl-4,4-dimethylpiperidine, N-acryloyl-2,2,6,6-tetramethylpiperidine, N-acryloyl-2-methyl-5-ethylpiperidine, N-acryloyl-4-methyl-4-ethylpiperidine, N-acryloyl-2-ethylpiperidine, N-acryloyl N-Acryloyl-3-ethylpiperidine, N-Acryloyl-4-ethylpiperidine, N-Acryloyl-2-propylpiperidine, N-Acryloyl-3-propylpiperidine, N-Acryloyl-4-propylpiperidine, N-Acryloyl-3-isopropylpiperidine, N-Acryloyl-4-isopropylpiperidine, N-Acryloylhexamethyleneimine, N-Acryloyl-2-methylhexamethyleneimine, N-Acryloyl-3-methylhexamethyleneimine, N-Acryloyl-4-methylhexamethyleneimine Hexamethyleneimine, N-acryloyl-2-ethylhexamethyleneimine, N-acryloyl-3-ethylhexamethyleneimine, N-acryloyl-4-ethylhexamethyleneimine, N-acryloyl-3-propylhexamethyleneimine, N-acryloyl-4-propylhexamethyleneimine, N-acryloyl-3-isopropylhexamethyleneimine, N-acryloyl-4-isopropylhexamethyleneimine, N-acryloyl-3,5-dimethylhexamethyleneimine, N-acryloyl-4,Examples of suitable acrylamides include 4-dimethylhexamethyleneimine, N-acryloylheptamethyleneimine, N-acryloyloctamethyleneimine, N-acryloyldecamethyleneimine, dopamine acrylamide, and 3-acrylamidophenylboronic acid. Among these, N-cyclohexyl acrylamide, N,N-dicyclohexyl acrylamide, N-cyclohexyl-N-methylacrylamide, N-acryloylmorpholine, N-acryloylpiperidine, N-acryloyl-2-methylpiperidine, N-acryloyl-4-methylpiperidine, N-acryloyl-2,6-dimethylpiperidine, N-acryloyl-3,5-dimethylpiperidine, N-phenylacrylamide, dopamine acrylamide, and 3-acrylamidophenylboronic acid are preferred, due to the ease of obtaining industrial products.
[0030] In the above b2, examples of the polyfunctional polymerizable compound having an acrylamide group include polyfunctional polymerizable compounds having an acrylamide group, such as oligomer-type polyurethane diacrylamide having a cyclic substituent. These polyfunctional polymerizable compounds having an acrylamide group may be used alone or in combination of two or more.
[0031] Examples of the monofunctional polymerizable compound having an acrylate group in b2 include phenoxyethyl acrylate, phenoxydiethylene glycol acrylate, phenoxytetraethylene glycol acrylate, phenoxyhexaethylene glycol acrylate, cyclohexyl acrylate, tert-butylcyclohexyl acrylate, benzyl acrylate, dicyclopentanyl acrylate, dicyclopentenyl acrylate, bornyl acrylate, isobornyl acrylate, tetrahydrofurfuryl acrylate, 2-methyl-2-adamantyl (meth)acrylate, etc. Among these, from the viewpoint of easy availability of industrial products, phenoxyethyl acrylate, cyclohexyl acrylate, tert-butylcyclohexyl acrylate, dicyclopentanyl acrylate, dicyclopentenyl acrylate, isobornyl acrylate, and tetrahydrofurfuryl acrylate are preferred.
[0032] Examples of the polyfunctional polymerizable compound having an acrylate group in b2 include monomer-type polyfunctional polymerizable compounds having an acrylate group, such as dicyclopentanyl diacrylate, caprolactone-modified dicyclopentenyl diacrylate, tricyclodecane dimethanol diacrylate, ethylene oxide-modified bisphenol A diacrylate, propylene oxide-modified bisphenol A diacrylate, and cyclohexane dimethanol diacrylate, as well as oligomer-type polyfunctional polymerizable compounds having an acrylate group, such as polyurethane diacrylate having a cyclic substituent, polyester diacrylate having a cyclic substituent, and polyether diacrylate having a cyclic substituent. These polyfunctional polymerizable compounds having an acrylate group may be used alone or in combination of two or more.
[0033] The monofunctional polymerizable compound in the active energy ray-curable composition (E), including the (meth)acrylate (A) and the polymerizable compound (B), preferably accounts for 5 to 99% by mass of the total of E. Furthermore, the polyfunctional polymerizable compound in E, including A and B, preferably accounts for 1 to 95% by mass of the total of E. As long as the monofunctional polymerizable compound and polyfunctional polymerizable compound in E are within these ranges, it becomes possible to easily combine compounds having different structures depending on the purpose, and E can be suitably used for various applications. From this perspective, the total amount of the monofunctional polymerizable compound in E is more preferably 10 to 90% by mass, and particularly preferably 20 to 80% by mass. Furthermore, the total amount of the polyfunctional polymerizable compound in E is more preferably 5 to 90% by mass, and particularly preferably 10 to 80% by mass.
[0034] A sixth embodiment of the present invention is an active energy ray-curable composition (E) having a volume shrinkage (curing shrinkage) of 5% or less that occurs during the curing process upon irradiation with active energy rays. Such an active energy ray-curable composition (E) preferably contains 5% by mass or more of a (meth)acrylate (A) and 60% by mass or less of a polyfunctional polymerizable compound as the polymerizable compound (B) relative to the total amount of E, and more preferably contains 8% or more of A and 50% by mass or less of a polyfunctional polymerizable compound as B. Furthermore, it is particularly preferred that the active energy ray-curable composition (E) contains 5% by mass or more of an oligomer-type polyfunctional polymerizable compound and / or 2% by mass or more of a polymer-type polyfunctional polymerizable compound as B relative to the total amount of E, since this allows the cured product to have good impact resistance while maintaining a low curing shrinkage.
[0035] A seventh embodiment of the present invention is an active energy ray-curable composition (E) having a saturated water absorption of 10% or less in a cured product of the active energy ray-curable composition. Preferably, E contains 5% by mass or more of a (meth)acrylate (A) and 20% by mass or more of a compound having a linear or cyclic substituent having 6 or more carbon atoms as a polymerizable compound (B), relative to the total amount of E. It is more preferable that E contains 10% or more of A and 25% by mass or more of b1 or b2 having a linear substituent having 6 or more carbon atoms as B. Furthermore, it is particularly preferable that E contains 8% by mass or more of an oligomer-type compound having a linear or cyclic substituent having 6 or more carbon atoms as B and / or 3% by mass or more of b1 or b2 having a polymer-type linear substituent having 6 or more carbon atoms, relative to the total amount of E, because this tends to result in a low water absorption of the resulting cured product and at the same time improve the durability of the cured product.
[0036] An eighth embodiment of the present invention is an ink composition (hereinafter also referred to as ink). The ink composition contains the actinic energy ray-curable composition (E) according to any one of the first to seventh embodiments. The ink composition preferably contains 3 to 50 mass% of a (meth)acrylate (A), 20 to 80 mass% of a polymerizable compound (b1), and 0 to 70 mass% of a polymerizable compound (b2), which are components of E. By containing A, the ink composition has high curability and the surface drying properties of the resulting printed surface are excellent. Furthermore, by containing b1, the viscosity of the ink composition can be easily adjusted, pigment dispersion is good when a pigment is blended, and the ink composition has high ejection stability during printing. When a polyfunctional compound is used as b1, the ink composition has sufficient curability even without containing b2, but by containing b2, both the curability of the ink composition and the surface drying properties of the resulting printed surface are improved. Furthermore, by combining A, b1, and b2, the viscosity of the ink composition can be suitably adjusted depending on the printing method, and the resulting printed surface has excellent print clarity. The ink composition can be applied to a substrate by any conventional method. The viscosity of the ink composition at 25°C is preferably less than 500 mPa·s, and more preferably less than 100 mPa·s, from the viewpoint of enabling application to a substrate by inkjet printing. After application to a substrate, the ink composition is cured by irradiation with active energy rays to form a printed surface (ink layer or print layer). From the viewpoint of achieving a good balance of printing properties, such as the viscosity, pigment dispersibility, curability, and ejection stability of the ink composition, as well as the surface dryness and clarity of the resulting printed surface, the ink composition preferably contains 8 to 45% by mass of A, 30 to 80% by mass of b1, and 5 to 65% by mass of b2, and more preferably contains 10 to 40% by mass of A, 40 to 60% by mass of b1, and 10 to 50% by mass of b2.
[0037] A ninth embodiment of the present invention is an ink composition for two-dimensional or three-dimensional modeling (hereinafter also referred to as a modeling ink composition or modeling ink). The modeling ink composition contains the active energy ray-curable composition (E) according to any one of the first to seventh embodiments. The modeling ink composition preferably contains 5 to 60 mass% of a (meth)acrylate (A), 15 to 80 mass% of a polymerizable compound (b1), and 10 to 80 mass% of a polymerizable compound (b2), which are components of E. By including component A, the modeling ink composition has low cure shrinkage, resulting in good modeling precision. The resulting modeled object has good strength and water resistance, and is particularly excellent in heat resistance and impact resistance. By including component b1, the viscosity of the modeling ink composition can be easily adjusted, resulting in high stability and modeling precision during modeling. By including component b2, the modeling ink composition has high curability and the resulting modeled object has high strength. When component b2 is an oligomer-type or polymer-type multifunctional compound, the water resistance and impact resistance of the resulting modeled object are both improved. Furthermore, by combining A, b1, and b2, the viscosity of the ink composition for modeling can be suitably adjusted depending on the modeling method, resulting in an excellent precision of the resulting modeled object. The ink composition for modeling is cured by irradiation with active energy rays simultaneously with or immediately after formation into a predetermined shape pattern to form a thin film, and a two-dimensional or three-dimensional model is formed by stacking the thin films. The modeling method is not particularly limited, but examples include a stereolithography method in which the ink composition is ejected using an inkjet method and cured by irradiation with active energy rays. In this case, from the viewpoint of stable ejection, the viscosity of the ink composition for modeling at 25°C is preferably 1 to 200 mPa·s, and the ejection temperature is preferably in the range of 20 to 100°C. From the viewpoint of enabling the obtained two-dimensional or three-dimensional model to exhibit a good balance of heat resistance, impact resistance, water resistance, high strength, and excellent modeling precision, the modeling ink composition preferably contains 5 to 50 mass% of A, 20 to 70 mass% of b1, and 15 to 75 mass% of b2, and more preferably contains 10 to 40 mass% of A, 30 to 60 mass% of b1, and 20 to 60 mass% of b2.
[0038] A tenth embodiment of the present invention is a pressure-sensitive adhesive composition (hereinafter also referred to as a pressure-sensitive adhesive). The pressure-sensitive adhesive composition contains the active energy ray-curable composition (E) according to any one of the first to seventh embodiments. The (meth)acrylate (A) and polymerizable compound (B) contained in the pressure-sensitive adhesive composition can be brought in from E containing A and B, or can be added directly when preparing the pressure-sensitive adhesive composition. The pressure-sensitive adhesive composition preferably contains A in a total content of 2 to 60 mass%, B in a total content of b1 in a total content of 5 to 75 mass%, and B in a total content of b2 in a total content of 10 to 80 mass%. Since A contains an amide group and a cyclic substituent, the pressure-sensitive adhesive composition has sufficient cohesive strength and adhesive strength, good adhesion to various substrates and good stain resistance, and low cure shrinkage, resulting in excellent durability of the resulting pressure-sensitive adhesive layer and pressure-sensitive adhesive laminate. Furthermore, by containing b1 and / or b2, the viscosity and curability of the pressure-sensitive adhesive composition can be easily adjusted according to the purpose, and the pressure-sensitive adhesive composition and the pressure-sensitive adhesive layer and pressure-sensitive adhesive laminate obtained by curing the same have good transparency. In particular, when 5 to 50 mass % of an oligomer-type or polymer-type polyfunctional compound (total of b1 and b2) is contained, the adhesive strength and durability of the pressure-sensitive adhesive layer after curing with active energy rays are high, which is more preferable. On the other hand, by crosslinking the pressure-sensitive adhesive composition using a crosslinking agent by the following crosslinking methods (1) to (3), it is also possible to obtain a pressure-sensitive adhesive layer and a pressure-sensitive adhesive laminate with better stain resistance and durability.
[0039] The crosslinking method of the tenth embodiment includes: (1) a method in which a pressure-sensitive adhesive composition contains a (meth)acrylate (A) and / or a polymerizable compound (B) having a reactive functional group (such as a hydroxyl group, an amino group, a carboxyl group, or an oxazoline group), introduces crosslinking points, and further contains a compound (crosslinking agent) having a functional group (such as an isocyanate group or a carboxyl group) that can react with these reactive functional groups, and crosslinks the composition by a crosslinking reaction; (2) a method in which a pressure-sensitive adhesive composition contains a multifunctional compound (monomer type, oligomer type, or polymer type) and crosslinks the composition by irradiation with active energy rays; and (3) a method in which a pressure-sensitive adhesive composition contains a multifunctional compound and A or B capable of introducing crosslinking points, and crosslinks the composition by irradiation with active energy rays and a crosslinking reaction. Note that (3) is a method that appropriately combines the crosslinking methods (1) and (2). In the present invention, examples of the crosslinking agent include polyisocyanate having two or more isocyanate groups in the molecule, polyepoxy having two or more epoxy groups in the molecule, polyaziridine having two or more aziridine groups in the molecule, polycarboxylic acid having two or more carboxyl groups in the molecule, polyoxazoline having two or more oxazoline groups in the molecule, etc. In the present invention, the crosslinking method is the same as in other embodiments.
[0040] The pressure-sensitive adhesive composition according to the tenth embodiment can be applied to or molded onto a separator or substrate, and then cured by irradiation with active energy rays to form a pressure-sensitive adhesive layer. When the pressure-sensitive adhesive composition contains an organic solvent, the composition may be applied to or molded onto a separator or substrate, irradiated with active energy rays, and cured while evaporating (drying) the organic solvent. However, a more transparent pressure-sensitive adhesive layer can be obtained by heating and drying at a temperature of 60 to 120°C for 1 to 30 minutes, followed by active energy curing, which is preferred. The pressure-sensitive adhesive composition can be applied to a separator or substrate by a conventionally known method, such as spin coating, spray coating, knife coating, dipping, gravure roll coating, reverse roll coating, screen printing, or bar coating.
[0041] A laminate can be obtained by laminating an adhesive layer made of the adhesive composition according to the tenth embodiment onto various substrates. Examples of methods for laminating the adhesive layer onto various substrates include a transfer method and a roll-to-roll method. The thickness of the adhesive layer in the laminate is not particularly limited because it differs depending on the intended use, but is typically 4 to 150 μm, and is preferably about 20 to 120 μm when used as an automotive component, and about 30 to 100 μm when used as an electronic material or optical component.
[0042] The substrate may be an organic substrate, an inorganic substrate, or a substrate made of an organic-inorganic composite material, having a wide range of polarities from low to high, depending on the intended use. Examples of suitable substrates include polyolefin resins such as polyethylene and polypropylene, polyester resins such as polyethylene terephthalate and polycarbonate, ABS resins (acrylonitrile-butadiene-styrene copolymers), acrylic resins such as polyimide resins, polyamide resins, and polymethyl methacrylate, metals such as steel, stainless steel, copper, and aluminum, glass, and hybrid materials in which inorganic silica particles are dispersed in organic polyimide. The intended uses of the resulting laminates are not particularly limited, and examples include electronic materials, optical components, and automotive components.
[0043] In a tenth embodiment, the adhesive composition of the present invention includes a (meth)acrylate (A) component having a hydrophobic cyclic substituent that exhibits wettability toward low-polarity substrates and a hydrophilic amide group that exhibits wettability toward high-polarity substrates within the molecule, thereby providing excellent adhesion to substrates ranging from low to high polarity. Furthermore, the strong cohesive force resulting from hydrogen bonding between the amide groups within the A molecules provides high adhesive strength and contamination resistance. Furthermore, the high refractive index of A and the good compatibility between A and the polymerizable compound (B) provide the adhesive composition with high transparency and yellowing resistance. The resulting adhesive layer also has high transparency and yellowing resistance, making it suitable for use in the optical field, such as adhesives for optical components and adhesive sheets. Laminates comprising an adhesive layer having such properties and various substrates can be used as adhesive films or adhesive sheets for electronic materials, optical components, and automotive components. When A has different ethylenically unsaturated groups, some of the ethylenically unsaturated bonds can be photocured by irradiation with active energy rays, and the remaining ethylenically unsaturated bonds can then be thermally polymerized by heating. In such a hybrid curing method, after an adhesive layer or adhesive laminate is produced using active energy rays, the crosslinking reaction is further promoted by heating, allowing for peeling, reworking, recycling, etc., and by laminating the adhesive layer or adhesive laminate to an opaque substrate such as a metal after irradiation with active energy rays and heating the laminate, it is possible to achieve adhesion of semi-transparent or opaque substrates using active energy rays, and it is also possible to obtain adhesive laminates formed from different materials.
[0044] An eleventh embodiment of the present invention is an adhesive composition (hereinafter also referred to as an adhesive). The adhesive composition contains the active energy ray-curable composition (E) according to any of the first to seventh embodiments. In this embodiment, a crosslinking agent may be contained, and crosslinking may be performed by the various crosslinking methods described above. Like the pressure-sensitive adhesive composition described above, the adhesive composition contains a (meth)acrylate (A), which can provide good adhesion to substrates ranging from low polarity to high polarity. Furthermore, by combining A with a polymerizable compound (B), various substrates, including organic substrates, inorganic substrates, and organic-inorganic composite materials, can be bonded by various curing methods. The cured adhesive layer exhibits high adhesive strength and impact resistance, and can be used as an adhesive composition for homogeneous or heterogeneous materials. Among the various materials, such as the resin materials, metal materials, glasses, and hybrid materials described above, two or more of the same type of material are referred to as homogeneous materials, and two or more different types of material are referred to as heterogeneous materials.
[0045] The (meth)acrylate (A) and polymerizable compound (B) of the adhesive composition can be introduced from an active energy ray composition (E) containing A and B, or can be added directly when preparing the adhesive composition. The adhesive composition preferably contains 2 to 65% by mass of A in total, 0 to 75% by mass of b1 as B in total, and 5 to 90% by mass of b2 as B in total. By containing an amide group and a cyclic substituent, A provides sufficient cohesive strength and adhesion to various substrates as an adhesive composition, resulting in high adhesive strength of the adhesive layer after curing. The adhesive composition also exhibits low cure shrinkage and excellent impact resistance of the resulting adhesive layer and adhesive laminate. Furthermore, the viscosity of the adhesive composition and the content of the monofunctional polymerizable compound and polyfunctional compound as B can be easily adjusted depending on the substrate and curing method used. A content of the monofunctional polymerizable compound (total of b1 and b2) as B in the adhesive composition is preferably 25 to 60% by mass, as this facilitates adjustment of the viscosity of the adhesive composition and suppresses cure shrinkage. Furthermore, when the total content of the polyfunctional compounds (total of b1 and b2) as B is 15 to 60 mass %, the adhesive strength is high while high impact resistance is maintained, which is more preferable.
[0046] In a coating composition (hereinafter also referred to as an adhesive) according to a twelfth embodiment, the (meth)acrylate (A) and polymerizable compound (B) contained in the coating composition can be obtained from an active energy ray composition (E) containing A and B, or can be added directly when preparing the coating composition. The coating composition preferably contains 5 to 60 mass% of A in total, 5 to 65 mass% of b1 as B in total, and 10 to 80 mass% of b2 as B in total. By containing an amide group and a cyclic substituent, A provides high wettability to various substrates, high abrasion resistance to the cured coating film, low cure shrinkage of the coating composition, and no unevenness on the surface of the resulting cured coating film, resulting in excellent appearance. Furthermore, the viscosity of the coating composition and the content of the monofunctional polymerizable compound and polyfunctional compound as B can be easily adjusted depending on the substrate and curing method used. From the viewpoint of enabling the coating composition to have a wide range of viscosity adjustment from low to high, it is preferable that the content of the monofunctional polymerizable compound (b1 and b2) as B be 0 to 60 mass% and the content of the oligomer-type or polymer-type polymerizable compound (b1 and b2) as B be 5 to 40 mass%. Furthermore, it is more preferable that the content of the polyfunctional compound (b1 and b2) as B be 15 to 85 mass%, since this results in high abrasion resistance while maintaining excellent appearance of the cured coating film. Furthermore, two-stage irradiation with UV rays and EB rays as active energy rays does not leave any monomer in the cured coating film, and the appearance of the cured coating film does not change (deteriorate) over time. In particular, when the cyclic substituent of A has an unsaturated bond, UV rays and EB rays can cause a stepwise photo-curing reaction between the (meth)acrylate group of A and the unsaturated bond of the cyclic substituent, further improving the abrasion resistance of the resulting cured coating film.
[0047] In the sealant composition according to the thirteenth embodiment, the (meth)acrylate (A) and polymerizable compound (B) contained in the sealant composition can be brought in from an active energy ray composition (E) containing A and B, or can be added directly when preparing the sealant composition. The sealant composition preferably contains A in a total content of 5 to 60 mass%, B in a total content of b1 in a total content of 0 to 70 mass%, and B in a total content of b2 in a total content of 10 to 70 mass%. By containing an amide group and a cyclic substituent, A exhibits low cure shrinkage of the sealant composition and provides excellent heat-sealing resistance for the resulting sealant. Furthermore, by including b1 and / or b2, the viscosity, curing method, and curability of the sealant composition can be easily adjusted according to the purpose, and the sealant obtained upon curing exhibits a high sealing effect, good resistance to moist heat yellowing, and good corrosion resistance, which is preferable. In particular, when the polyfunctional compound of oligomer type or polymer type (total of b1 and b2) is contained in an amount of 2 to 45 mass %, the sealant has low water absorption and high outgassing resistance after being cured with active energy rays, which is more preferable.
[0048] In the nail cosmetic according to the fourteenth embodiment, the (meth)acrylate (A) and polymerizable compound (B) contained in the nail cosmetic can be obtained from an active energy ray-emitting composition (E) containing A and B, or can be added directly during preparation of the nail cosmetic. The nail cosmetic preferably contains 1 to 30% by mass of A in total, 10 to 65% by mass of b1 in total as B, and 5 to 70% by mass of b2 in total as B. By containing an amide group and a cyclic substituent, A exhibits low cure shrinkage of the nail cosmetic, and the resulting cured film exhibits excellent adhesion and surface hardness. Furthermore, the inclusion of b1 and / or b2 makes it easier to adjust the viscosity, curing method, and curability of the nail cosmetic according to the intended purpose, and the resulting cured nail cosmetic film exhibits high surface gloss, making this more preferable.
[0049] In the decorative coating agent according to the fifteenth embodiment, the (meth)acrylate (A) and polymerizable compound (B) contained in the decorative coating agent can be introduced from an active energy ray composition (E) containing A and B, or can be added directly when preparing the decorative coating agent. The decorative coating agent preferably contains A in a total content of 1 to 50 mass%, B in a total content of b1 in a total content of 10 to 60 mass%, and B in a total content of b2 in a total content of 15 to 70 mass%. Since A contains an amide group and a cyclic substituent, the cure shrinkage of the decorative coating agent is low, and the resulting decorative coating film has excellent elongation and bending resistance. Furthermore, by appropriately adjusting the content of b1 and / or b2, the tack resistance and pencil hardness of the resulting decorative coating film can be improved. Furthermore, after curing with active energy rays and / or decorative molding such as stretching of the cured film, the residual monomers are thermally polymerized by heat treatment, and in particular, when the cyclic substituent of A has an unsaturated bond, the crosslinking rate of the decorative coating film is increased by the thermal polymerization of the unsaturated bond, thereby further improving the scratch resistance and sunscreen resistance of the coating film.
[0050] In the dental material according to the sixteenth embodiment, the (meth)acrylate (A) and polymerizable compound (B) contained in the dental material can be obtained from an active energy ray-emitting composition (E) containing A and B, or can be added directly during preparation of the dental material. The dental material preferably contains 0.5 to 50% by mass of A in total, 5 to 70% by mass of b1 in total, and 10 to 60% by mass of b2 in total. By containing an amide group and a cyclic substituent, A exhibits low cure shrinkage and excellent surface smoothness and adhesive strength in the resulting cured dental material. Furthermore, by appropriately adjusting the content of b1 and / or b2, the solubility and dispersibility of the dental material, as well as the curability and hardness of the cured product, can be improved. Furthermore, after curing with active energy rays, thermal polymerization of residual monomers by heat treatment, particularly when the cyclic substituent of A contains an unsaturated bond, can further enhance the adhesive strength of the cured dental material through thermal polymerization of the unsaturated bond.
[0051] The active energy ray-curable compositions (E) according to the first to seventh embodiments of the present invention may contain various additives other than those described above, as necessary. Examples of additives include thermal polymerization inhibitors, antioxidants, ultraviolet sensitizers, preservatives, phosphate esters and other flame retardants, surfactants, antistatic agents, colorants such as pigments and dyes, fragrances, antifoaming agents, fillers, silane coupling agents, surface tension modifiers, plasticizers, surface lubricants, leveling agents, softeners, organic fillers, inorganic fillers, and silica particles. These additives may be used alone or in combination of two or more. The content of these additives is not particularly limited as long as it does not adversely affect the properties of various molded articles of E, but is preferably 5% by mass or less based on the total weight of E.
[0052] The compositions according to the eighth to sixteenth embodiments of the present invention may contain various additives other than those described above, as needed. Examples of such additives include thermal polymerization inhibitors, antioxidants, UV sensitizers, preservatives, phosphate esters and other flame retardants, surfactants, antistatic agents, colorants such as pigments and dyes, fragrances, defoamers, fillers, silane coupling agents, surface tension modifiers, plasticizers, surface lubricants, leveling agents, softeners, organic fillers, inorganic fillers, and silica particles. These additives may be used alone or in combination of two or more. The content of these additives is not particularly limited as long as it does not adversely affect the properties of various molded articles obtained from the compositions, but is preferably 30 wt% or less based on the total weight of the composition. Furthermore, water, organic solvents, and mixtures thereof may be used as solvents or diluents, as needed. The content of such solvents is not particularly limited as long as it does not adversely affect the properties of various molded articles obtained from the compositions, but is preferably 95 wt% or less based on the total weight of the composition.
[0053] The active energy ray-curable composition (E) may further contain a polymerization initiator. In this case, E has improved curability upon irradiation with active energy rays, and can be suitably used as an active energy ray-curable ink composition according to other embodiments of the present invention, a composition for two-dimensional or three-dimensional modeling, a pressure-sensitive adhesive composition, an adhesive composition, a paint composition, a sealant composition, a nail cosmetic, a decorative coating agent, a dental material, a water-resistant paint composition, a coating agent for vehicles, and a coating agent for indoor and / or outdoor building materials, etc.
[0054] In this specification, active energy rays are defined as energy rays that can decompose a compound (photopolymerization initiator) that generates active species to generate active species. Examples of such active energy rays include visible light, ultraviolet light, infrared light, α-rays, β-rays, γ-rays, X-rays, and electron beams (EB). When electron beams are used as active energy rays, a photopolymerization initiator does not need to be used. On the other hand, when ultraviolet light or visible light is used, a photopolymerization initiator is preferably used. Irradiation with active energy rays is preferably carried out in an inert gas atmosphere such as nitrogen gas or carbon dioxide gas, or in an atmosphere with a reduced oxygen concentration. However, the active energy ray-curable composition (E) according to each embodiment of the present invention and the curable compositions containing E for various applications have good curability due to the presence of a (meth)acrylate (A) and a polymerizable compound (B), and can be sufficiently cured even in an ordinary air atmosphere. The irradiation temperature for active energy rays is preferably 10°C to 200°C, and the irradiation time is preferably 1 second to 60 minutes.
[0055] The photopolymerization initiator may be any substance that generates radicals upon irradiation with active energy rays (i.e., photoradical polymerization initiator). Examples of the photopolymerization initiator include benzoins such as benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin isobutyl ether, and anisole methyl ether; 4-(2-hydroxyethoxy)phenyl(2-hydroxy-2-propyl)ketone, α-hydroxy-α,α'-dimethylacetophenone, methoxyacetophenone, 2,2'-dimethoxy-2-phenylacetophenone, 2-hydroxy-2-cyclohexylacetophenone, 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 1-hydroxycyclohexylphenyl ketone, acetophenones such as 4-phenoxydichloroacetophenone and 4-t-butyldichloroacetophenone; propiophenones such as 2-hydroxy-2-methylpropiophenone and 2-hydroxy-4'-isopropyl-2-methylpropiophenone; benzophenones, benzophenones such as thioxanthone, 2-chlorothioxanthone, 2-ethylthioxanthone, 2-isopropylthioxanthone, 2,4-dichlorothioxanthone, 2,4-diethylthioxanthone, 2,4-diisopropylthioxanthone, and dodecylthioxanthone; acylphosphine oxides such as bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-2,4-di-n-butoxyphenylphosphine oxide, and bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphenylphosphine oxide; benzyl dibenzosuberone; and α-acyloxime esters.Commercially available photopolymerization initiators that can be used include those manufactured by IGM Resins BV under the trade names Omnirad 1116, Omnirad 1173, Omnirad 184, Omnirad 369, Omnirad 500, Omnirad 651, Omnirad 754, Omnirad 819, Omnirad 907, Omnirad 1300, Omnirad 1800, Omnirad 1870, Omnirad 2959, Omnirad 4265, and Omnirad TPO, and those manufactured by UCB under the trade name Ubecryl P36. These photopolymerization initiators may be used alone or in combination of two or more.
[0056] The content of the photopolymerization initiator is typically 0.1 to 30% by mass, preferably 0.5 to 20% by mass, and more preferably 0.5 to 3% by mass, based on the total mass of the various curable compositions according to the embodiments of the present invention. While depending on the type of photopolymerization initiator, the type of active energy ray, and the illuminance, a content of less than 0.1% by mass may result in insufficient curability, while a content of more than 30% by mass may result in reduced performance, such as reduced strength, of the cured product. In this specification, a compound having both a functional group with photopolymerization initiation function and an ethylenically unsaturated group in its molecule can be used as the polymerizable photopolymerization initiator. Depending on the number of ethylenically unsaturated groups contained therein, it can be classified as a monofunctional or polyfunctional polymerizable photopolymerization initiator. When a polymerizable photopolymerization initiator is contained, it can be used alone or without the use of a commercially available photopolymerization initiator.
[0057] The active energy ray-curable composition (E) may further contain a non-polymerizable oligomer and / or a non-polymerizable polymer. In this specification, those having an ethylenically unsaturated group in the molecule and having a weight-average molecular weight (Mw) of 1,000 or more but less than 10,000 are classified as non-polymerizable oligomers, and those having an Mw of 10,000 or more are classified as non-polymerizable polymers. Examples of non-polymerizable oligomers and non-polymerizable polymers include thermoplastic resins, rosin-based resins, and mixtures thereof. Examples of thermoplastic resins include (meth)acrylic resins, cyclic polyolefin resins, cellulose resins, polyester resins, polyurethane resins, polysulfonic acid resins, ABS resins, polycarbonate resins, polyamide resins, and polyimide resins. Examples of rosin-based resins include natural rosins such as gum rosin, and modified rosin resins such as hydrogenated rosins obtained by modifying natural rosin, disproportionated rosin, rosin-modified phenolic resins, maleic acid-modified rosin resins, maleated rosin, and esterified gum. These non-polymerizable oligomers and / or non-polymerizable polymers may be used alone or in combination of two or more.
[0058] The total content of the non-polymerizable oligomer and the non-polymerizable polymer is typically 0.1 to 20 mass%, preferably 0.5 to 15 mass%, and more preferably 1 to 10 mass%, based on the total mass of the various curable compositions according to the embodiments of the present invention. The inclusion of the non-polymerizable oligomer and the non-polymerizable polymer may reduce the cure shrinkage of the active energy ray-curable composition (E) and curable compositions containing the same used for various applications, adjust the viscosity, improve wettability and adhesion to substrates, and improve the surface hardness, tensile strength, water resistance, heat resistance, impact resistance durability, abrasion resistance, etc. of the resulting cured film and cured product, and may be suitably used depending on the purpose. [Example]
[0059] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples. The abbreviations for the components described in the examples and comparative examples are as follows. In the following, "parts" and "%" are all by mass unless otherwise specified. (1) (Meth)acrylate (A) Table 1 shows the (meth)acrylates (A-1) to (A-15) used in the examples.
[0060] (2) Polymerizable compound (B) <Polymerizable Compound (b1) Having a Chain Substituent Having 1 to 36 Carbon Atoms> b1-1: Dimethylacrylamide (registered trademark "Kohshylmer", "DMAA") b1-2: Diethylacrylamide (registered trademark "Kohshylmer", "DEAA") b1-3: Isopropylacrylamide (registered trademark "Kohshylmer", "NIPAM") b1-4: N-(2-hydroxyethyl)acrylamide (registered trademark "Kohshylmer", "HEAA") b1-5: N-[3-(dimethylamino)]propylacrylamide (registered trademark "Kohshylmer", "DMAPAA") b1-6: Diacetone acrylamide (registered trademark "Kohshylmer") b1-7: 2-ethylhexyl acrylate b1-8: 2-(2-ethoxyethoxy)ethyl acrylate b1-9: 4-hydroxybutyl acrylate B1-10: Pentaerythritol triacrylate b1-11: Dipentaerythritol hexaacrylate b1-12: 1,6-hexanediol diacrylate B1-13: Tripropylene glycol diacrylate <Polymerizable Compound (b2) Having a Cyclic Substituent Having 3 to 20 Carbon Atoms> b2-1: N-cyclohexyl acrylamide (registered trademark "Kohshylmer") b2-2: N-acryloylmorpholine (registered trademark "Kohshylmer", "ACMO") b2-3: N-phenylacrylamide (registered trademark "Kohshylmer") b2-4: Dopamine acrylamide (registered trademark "Kohshylmer") b2-5: 3-Acrylamide phenylboronic acid (registered trademark "Kohshylmer") B2-6: tert-butylcyclohexyl acrylate (registered trademark "Kohshylmer") b2-7: Isobornyl acrylate B2-8: Tetrahydrofurfuryl acrylate B2-9: Tricyclodecane dimethanol diacrylate b2-10: UV-3000B: Bifunctional urethane acrylate (Shiko, manufactured by Mitsubishi Chemical Corporation) b2-11: UV-6640B: Bifunctional urethane acrylate (Shiko, manufactured by Mitsubishi Chemical Corporation) b2-12: Quick Cure 7100: UV-curable urethane oligomer (registered trademark "Quick Cure", manufactured by KJ Chemicals) b2-13: Quick Cure 8100: UV-curable urethane oligomer (registered trademark "Quick Cure", manufactured by KJ Chemicals) <Polymerizable Compound (b3) (excluding A, b1, and b2)> b3-1: glycidyl methacrylate b3-2: 2-vinyl-2-oxazoline b3-3: acrylonitrile b3-4: acrylic acid
[0061] (3) Photopolymerization initiator (C) C-1: Omnirad 184 (photopolymerization initiator, manufactured by IGM Resins BV) C-2: Omnirad 1173 (photopolymerization initiator, manufactured by IGM Resins BV) C-3: Omnirad TPO (photopolymerization initiator, manufactured by IGM Resins BV)
[0062] (4) Other D-1: Hydrogenated rosin (non-polymerizable polymer, Tackyfire KE-359, manufactured by Arakawa Chemical Industries) D-2: Acrylic resin (non-polymerizable polymer, VS-1057, manufactured by Seiko PMC) D-3: Blenmer (non-polymerizable oligomer, PME-4000, manufactured by NOF Corporation) D-4: BYK-331 (leveling agent, polyether-modified polydimethylsiloxane, manufactured by BYK Chemie) D-5: Pigment dispersion (NX-061 Green, manufactured by Dainichiseika Color & Chemicals Mfg. Co., Ltd.) D-6: Hexamethylene diisocyanate D-7: Inorganic filler (titanium oxide) (5) Base material PP: Polypropylene board and film PC: Polycarbonate plate and film PMMA: Polymethyl methacrylate plates and films PET: Easy-to-adhere polyethylene terephthalate plate and film ABS: Acrylonitrile-butadiene-styrene copolymer synthetic resin board SPCC: Cold-rolled steel plate SUS: Stainless steel plate Al: Aluminum plate Cu: copper plate PO: Polyolefin sheet PVC: Polyvinyl chloride board HDF: Wood board (high density fiberboard)
[0063] <Preparation and Evaluation of Active Energy Ray-Curable Composition> Examples 1 to 16 and Comparative Examples 1 to 4 The (meth)acrylate (A), polymerizable compound (B) (b1 having a chain-like substituent and b2 having a cyclic substituent), photopolymerization initiator (C), and other components used in this embodiment were weighed out in the proportions shown in Table 2 and mixed uniformly at room temperature to prepare curable compositions of the Examples and Comparative Examples. The transparency (compatibility), curability, and cure shrinkage resistance of the resulting curable compositions were evaluated by the methods described below, and the results are shown in Table 2. In addition, the water resistance of the cured products obtained in each Example and Comparative Example was evaluated by the method described below, and the results are shown in Table 2.
[0064] <Evaluation of Transparency (Compatibility) of Curable Composition> The state of the active energy ray-curable compositions prepared in each of the Examples and Comparative Examples was visually observed, and the transparency (compatibility) was evaluated in four stages. ◎: High transparency, no turbidity or separation observed. Good: High transparency, but slight turbidity observed. △: No phase separation, but turbidity. ×: Turbidity or phase separation is observed.
[0065] <Curability evaluation (365nm, 385nm and 405nm)> The active energy ray-curable compositions prepared in each Example and Comparative Example were applied to the adhesively treated surface of a 100 μm-thick PET film (Cosmoshine A-4100, manufactured by Toyobo) using a bar coater to a film thickness of 20 μm. The coating was then cured by irradiating it with ultraviolet light, and the cumulative light dose required for the cured product to lose its tack when touched was determined, and the curability was evaluated on a four-point scale. The following three types of ultraviolet irradiating lamps, 1) to 3), were used. The lower the cumulative light dose required for the tack to disappear (complete curing), the higher the curability. 1) UV LED lamp: wavelength 365 nm, output 100 mW / cm 2 2) UV LED lamp: wavelength 385 nm, output 100 mW / cm 2 3) UV LED lamp: Wavelength 405 nm, output 100 mW / cm 2 ◎: Accumulated light intensity 200mJ / cm 2 Tack disappears below ○: Accumulated light intensity 200mJ / cm 2 More than 500mJ / cm 2 Tack disappears below △: Accumulated light intensity 500mJ / cm 2 More than 1000mJ / cm 2 Tack disappears below ×: Accumulated light intensity 1000mJ / cm 2 The tack will disappear (including cases where the tack does not disappear)
[0066] <Evaluation of cure shrinkage resistance> A silicone spacer (30 mm long x 15 mm wide x 1 mm thick) was placed on a glass plate (50 mm long x 50 mm wide x 5 mm thick), and the active energy ray-curable composition prepared in each Example and Comparative Example was poured into the spacer, followed by ultraviolet irradiation (apparatus: Inverter-type conveyor apparatus ECS-4011GX manufactured by Eye Graphics, metal halide lamp: M04-L41 manufactured by Eye Graphics, ultraviolet irradiance: 700 mW / cm 2 , Accumulated light intensity: 1000mJ / cm 2 ) to prepare a cured sheet. The cure shrinkage was determined in accordance with JIS K5600 2-4 from the change in density before and after curing of the active energy ray-curable composition as shown in the following calculation formula (1). The density of the curable composition before and after curing was measured using an electronic hydrometer (MDS-300 manufactured by Alpha Mirage Co., Ltd.) in accordance with JIS K7112. The density of the prepared cured sheet was taken as the density of the curable composition after curing, and the following evaluations were made based on the cure shrinkage. (Cure shrinkage rate) = (Ds - Dl) / Dl x 100 Calculation formula (1) (In the formula, Ds is the density of the curable composition after curing, and Dl is the density of the curable composition before curing.) ◎: The cure shrinkage rate is 3% or less. ◯: The cure shrinkage rate exceeds 3% but is 5% or less. △: The cure shrinkage rate exceeds 5% but is 8% or less. ×: The cure shrinkage rate exceeds 8%.
[0067] <Evaluation of water resistance of cured product> Cured sheets were prepared in the same manner as in the evaluation of cure shrinkage resistance described above. The resulting sheets were cut into 3 cm squares and dried under vacuum at 60°C for 24 hours. The dried sheets were then accurately weighed and used as the dry weight of the cured product. The dried sheets were immersed in deionized water at 30°C. After 24 and 48 hours, the weight was measured immediately after removal from the deionized water to confirm that the sheet had reached saturated water absorption, and this was used as the weight of the cured product in its saturated water absorption state. The saturated water absorption rate was calculated using the following formula, and the water resistance of the cured products was evaluated using the following four-point scale. Saturated water absorption rate (%) = (weight at saturated state - weight at dry state) / weight at dry state × 100% ◎: Saturated water absorption is 8% or less. ○: The saturated water absorption rate is more than 8% but is 10% or less. △: The saturated water absorption rate is more than 10% but is 20% or less. ×: Saturated water absorption exceeds 20%.
[0068] As is clear from the results in Table 2, the active energy ray-curable compositions of each Example contained a (meth)acrylate (A) having an amide group and a cyclic substituent in the molecule, and a polymerizable compound (b1) having a chain substituent having 1 to 36 carbon atoms and / or a polymerizable compound (b2) having a cyclic substituent having 3 to 20 carbon atoms. As a result, the active energy ray-curable compositions of each Example had good transparency (compatibility), high curability with respect to light of 365 nm, 385 nm, and 405 nm, and low cure shrinkage upon curing. It was also confirmed that the resulting cured products had excellent water resistance. On the other hand, in Comparative Examples 1 to 4, since the (meth)acrylate (A) and the polymerizable compound (B) (b1 and / or b2) were not simultaneously contained, none of the curable compositions were satisfactory in terms of transparency, curability, and cure shrinkage resistance. Furthermore, the cured products of the Comparative Examples had poor water resistance. It is believed that such different physical properties between the Examples and the Comparative Examples are due to the interaction between A and B contained in the active energy ray-curable compositions of the present invention, as described above.
[0069] <Preparation and Evaluation of Actinic Energy Ray-Curable Ink Composition> Examples 17 to 22 and Comparative Examples 5 to 8 The active energy ray-curable composition obtained in Table 2, (meth)acrylate (A), polymerizable compound (B), photopolymerization initiator (C), and other components were weighed in the proportions shown in Table 3 and mixed uniformly at room temperature to prepare ink compositions of Examples and Comparative Examples. Using the prepared ink compositions, viscosity measurements were performed using the following method, and pigment dispersibility was also evaluated when a pigment dispersion was contained. The active energy ray curability of the ink compositions and the surface drying properties of the resulting cured films were evaluated. In addition, inkjet printing was performed, and the ink ejection stability and clarity of the printed matter were evaluated as printability. The results of these evaluations are summarized in Table 3. Example 18 is an example in which curing was performed by irradiation with electron beams (EB) instead of ultraviolet light. The EB irradiation device used was a Curetron EBC-200-AA3 manufactured by Nissin High Voltage Corporation (accelerating voltage: 200 kV, exposure dose: 20 kGy).
[0070] <Viscosity measurement and evaluation> The viscosity of the ink composition was measured in accordance with JIS K5600-2-3 using a cone-plate viscometer (RE550 viscometer manufactured by Toki Sangyo Co., Ltd.) As an ink composition for inkjet printing, the viscosity was evaluated into the following four levels. ◎: 5 or more, less than 100 mPa·s ○: 100 or more, less than 500 mPa·s △: 500 or more, less than 2000 mPa·s ×:2000mPa·s or more
[0071] <Evaluation of pigment dispersibility> The prepared ink compositions were visually observed for aggregation and precipitation of the pigment immediately after preparation and after being left to stand at room temperature for 2 months, and the pigment dispersibility was evaluated into the following four levels. ⊚: No aggregation or precipitation of the pigment was observed immediately after preparation or after leaving it to stand for 2 months. ◯: No precipitation of pigment was observed immediately after preparation, but slight precipitation of pigment was observed after leaving it to stand for 2 months. △: Slight aggregation and precipitation of pigments was observed immediately after preparation, but after leaving the mixture to stand for 2 months, aggregation and precipitation of pigments was clearly observed. ×: Pigment aggregation and precipitation were clearly observed even immediately after preparation.
[0072] Method for producing printed matter by irradiation with active energy rays The obtained ink composition was applied to a 100 μm thick PET film using a bar coater (RDS12) (film thickness after drying: 10 μm), and cured by ultraviolet irradiation (inverter type conveyor device ECS-4011GX, metahalide lamp M04-L41, manufactured by iGraphics Co., Ltd.) to produce a printed material.
[0073] <Evaluation of Curability of Ink Composition> When a printed matter was produced by the above method, the cumulative amount of light until the ink composition was completely cured (to a non-sticky state) was measured, and the curability was evaluated. ◎: 1000mJ / cm 2 Completely cured in less than ○: 1000 or more, 2000mJ / cm 2 Completely cured in less than △:2000 or more, 5000mJ / cm 2 Completely cured in less than ×: 5000mJ / cm until complete curing 2 More than necessary
[0074] <Surface drying evaluation> The printed matter produced by the above method was left to stand for 5 minutes in an environment with a room temperature of 23°C and a relative humidity of 50%, and then a sheet of high-quality paper was placed on the printed surface and a load of 1 kg / cm was applied. 2 The load was applied for 1 minute and the degree of ink transfer to the paper was evaluated. ⊚: The ink was dry and not transferred to the paper at all. ○: The ink was dried and there was a small amount of transfer to the paper. △: The ink was almost dry and was transferred to the paper. ×: The ink was barely dried and much was transferred to the paper.
[0075] <Inkjet printing and printability evaluation> The prepared ink composition was filled into a commercially available inkjet printer (LuxelJet U V350GTW manufactured by Fujifilm Corporation), and a solid image was printed on coated paper, and the printability of the ink was evaluated by the following method.
[0076] <Evaluation of ejection stability> The print quality of the inkjet printed matter was evaluated visually. ⊚: No nozzles missing, printing was good. ○: There is a slight nozzle missing. △: Missing nozzles over a wide area. ×: Non-ejection occurs.
[0077] <Clarity evaluation> The image clarity of the ink-jet printed matter obtained from the ink composition containing the pigment was visually observed. ⊚: No ink bleeding was observed and the image was clear. ◯: There was almost no ink bleeding and the image was good. △: Slight ink bleeding was observed. ×: Significant ink bleeding was observed.
[0078] The viscosity of the actinic radiation-curable ink composition of the present invention can be adjusted as desired to suit various printing methods, such as inkjet printing, offset printing, screen printing, and flexographic printing. As is clear from the results in Table 3, the ink composition can be adjusted to a low viscosity for inkjet printing, and when a pigment is incorporated, it exhibits high pigment dispersibility. These results are due to the excellent compatibility between the (meth)acrylate (A) and polymerizable compound (B) contained in the examples, the wide variety of polymerizable compounds (b1) having a chain substituent and the polymerizable compound (b2) having a cyclic substituent, ranging from low to high viscosity, and the ease of combining them with other components such as pigment dispersants. Furthermore, by combining A with b1 and / or b2, the ink compositions of the examples exhibited high curability, the resulting cured films exhibited good surface drying properties, and the print clarity of the printed matter, which is an indication of the printability of the inkjet ink composition, was excellent. On the other hand, the ink compositions of the comparative examples all failed to provide satisfactory viscosity, pigment dispersibility, curability, surface drying properties, and inkjet printability.
[0079] <Preparation and Evaluation of Actinic Energy Ray-Curable Ink Composition for Three-Dimensional Modeling> Examples 23 to 29 and Comparative Examples 9 and 10 The active energy ray-curable composition obtained in Table 2, (meth)acrylate (A), polymerizable compound (B), photopolymerization initiator (C), and other components were weighed out in the proportions shown in Table 4 and mixed uniformly at room temperature to prepare ink compositions for three-dimensional modeling of Examples and Comparative Examples. Three-dimensional models were produced using the ink compositions for three-dimensional modeling by the following method, and the strength, heat resistance, and modeling accuracy of the resulting cured products were evaluated. The evaluation results are shown in Table 4.
[0080] <Strength evaluation> A 75 μm thick heavy release PET film (Toyobo Co., Ltd., polyester film E7001) was placed in close contact with a horizontally placed glass plate, and a 1 mm thick spacer punched into a No. 2 dumbbell shape conforming to JIS K6251 was placed inside the spacer. The ink composition for three-dimensional modeling obtained in each example and comparative example was then filled inside the spacer. A 50 μm thick light release PET film (Toyobo Co., Ltd., polyester film E7002) was then placed on top of the spacer, and ultraviolet light was irradiated from both sides (device: Eye Graphics, inverter type conveyor device ECS-4011GX; metal halide lamp: Eye Graphics, M04-L41; ultraviolet irradiance: 200 mW / cm). 2 , cumulative light intensity 1000mJ / cm 2 ) to cure the ink composition for three-dimensional modeling. The release PET films on both sides were then removed to obtain test pieces of the cured product for the examples and the comparative examples. According to JIS K7161, the tensile strength was measured using a bench-top precision universal testing machine (Shimadzu Corporation, Autograph AGS-X) at a temperature of 25°C, with a tensile speed of 10 mm / min and a chuck distance of 50 mm, and the strength was evaluated according to the following criteria. ◎: Tensile strength 40 MPa or more ○: Tensile strength 30 MPa or more and less than 40 MPa △: Tensile strength 20MPa or more and less than 30MPa ×: Tensile strength less than 20 MPa
[0081] <Heat resistance evaluation> Cured products were prepared in the same manner as the test pieces for the tensile tests, and the glass transition temperatures (Tg) of the cured products were measured using a differential scanning calorimeter (DSC-60plus, manufactured by Shimadzu Corporation). The heat resistance was evaluated as follows based on the measured glass transition temperatures (Tg) of the cured products. ○: Cured product Tg 80℃ or higher △: Tg of cured product 40℃ or higher but lower than 80℃ ×: Tg of cured product less than 40°C
[0082] <Impact resistance evaluation> A 75 μm thick heavy-release PET film (Toyobo Co., Ltd., polyester film E7001) was placed in close contact with a horizontally placed glass plate, a 4 mm thick spacer with an internal dimension of 10 × 80 mm was placed, and the ink composition for three-dimensional modeling obtained in each example and comparative example was filled to a thickness of 4 mm inside the spacer. Then, a 50 μm thick light-release PET film (Toyobo Co., Ltd., polyester film E7002) was placed on top of the ink composition, and ultraviolet light was irradiated from both sides (device: Eye Graphics, inverter type conveyor device ECS-4011GX; metal halide lamp: Eye Graphics, M04-L41; ultraviolet irradiance: 200 mW / cm). 2 , cumulative light intensity 1,000mJ / cm 2 ) to cure the ink composition. Thereafter, the release PET films on both sides were removed, and the ink composition was further irradiated with ultraviolet light at a predetermined cumulative light intensity (apparatus: ITEC System Co., Ltd., tabletop batch-type UV-LED curing apparatus MUVBA-0.3×0.3×0.5, wavelength 405 nm, illuminance (UV-V) 50 mW / cm 2 , cumulative light intensity 5,000mJ / cm 2 ), and post-cure were performed to allow the material to completely cure. The resulting cured material was then used as a test piece to measure Izod impact strength (with notch) in accordance with JIS K-7110, and the impact resistance was evaluated as follows. An Izod-Charpy impact tester, Model No. 195-R, manufactured by Yasuda Seiki Seisakusho Co., Ltd., was used. Note that the higher the impact strength, the higher the impact resistance. ◎:40J / m or more ○: 30J / m or more but less than 40J / m △: 20J / m or more and less than 30J / m ×: Less than 20 J / m
[0083] <Water resistance evaluation> Using a 10 mm thick spacer with an internal dimension of 10 cm x 1 cm, cured test pieces for evaluating water resistance, measuring 10 cm long x 1 cm wide x 1 mm thick, were prepared in the same manner as in the strength evaluation and test piece preparation described above. The weight of the resulting test piece was measured immediately after molding, and then it was immersed in a beaker containing 100 ml of water. After one day, the weight after immersion was measured. The weight before immersion and the weight after immersion were substituted into the following equation to measure the water absorption, and water resistance was evaluated according to the criteria shown below. The lower the water absorption, the higher the water resistance. ◎: Water absorption rate is less than 2% ○: Water absorption rate is 2% or more and less than 2.5% △: Water absorption rate is 2.5% or more and less than 3% ×: Water absorption rate is 3% or more
[0084] <Modeling accuracy evaluation> A 75 μm thick heavy-release PET film (Toyobo Co., Ltd., Polyester Film E7001) was attached to a horizontally placed glass plate, and a 10 mm thick spacer with an internal dimension of 10 × 10 mm was placed. The spacer was filled with the ink composition for three-dimensional modeling obtained in each Example and Comparative Example to a thickness of 1 mm. The surface was then smoothed by incubating at 60°C for 30 seconds, and then irradiated with ultraviolet light (apparatus: Eye Graphics, inverter type conveyor device ECS-4011GX; metal halide lamp: Eye Graphics, M04-L41; ultraviolet irradiance: 200 mW / cm). 2 ) and the ink composition for three-dimensional modeling was cured. Thereafter, the ink composition for three-dimensional modeling was filled to a thickness of 1 mm, and the curing process was repeated 10 times to obtain a cured product measuring 10 x 10 x 10 mm. The height of the obtained cured product was measured. In addition, the side surface of the obtained cured product was visually observed. These results were combined and the modeling accuracy was evaluated according to the following criteria. ◎: Height is less than 10mm ± 0.1mm and there are no irregularities on the side. ○: Height is 10mm ±0.1mm or more but less than ±0.2mm, or there is slight unevenness on the side. △: Height 10mm ±0.2mm or more but less than ±0.3mm, or there are slight irregularities on the side. ×: Height is 10 mm ± 0.3 mm or more, or there are obvious irregularities on the side.
[0085] As is clear from the results in Table 4, the ink compositions for three-dimensional modeling of the examples have excellent resistance to cure shrinkage, and by using them, three-dimensional stereolithography objects can be obtained with high modeling precision. Furthermore, the heat resistance and impact resistance of the resulting objects are very good, and sufficient strength and water resistance can be obtained by adjusting the type and content of the (meth)acrylate (A) and polymerizable compound (B). Objects with such good properties were not obtained from the compositions of the comparative examples.
[0086] <Preparation and Evaluation of Pressure-Sensitive Adhesive Composition> Examples 30 to 35 and Comparative Examples 11 and 12 The active energy ray-curable composition obtained in Table 2, (meth)acrylate (A), polymerizable compound (B), photopolymerization initiator (C), and other components were weighed out in the proportions shown in Table 5 and mixed uniformly at room temperature to prepare pressure-sensitive adhesive compositions of the Examples and Comparative Examples. Pressure-sensitive adhesive layers and pressure-sensitive adhesive sheets were produced using the pressure-sensitive adhesive compositions by the methods described below. The curability of the pressure-sensitive adhesive compositions, adhesion to various substrates, and the transparency, adhesive strength, stain resistance (reworkability), durability, and yellowing resistance of the resulting pressure-sensitive adhesive layers were evaluated, and the results are shown in Table 5. In Examples 30 and 33, the pressure-sensitive adhesive sheets after being cured with active energy rays were placed in a thermostatic chamber at 80°C and aged for 48 hours to complete the crosslinking reaction, after which the various physical properties of the pressure-sensitive adhesive layers were evaluated.
[0087] <Evaluation of adhesive curing properties> A 75 μm thick heavy-release PET film (Toyobo Co., Ltd., polyester film E7001) was attached to a horizontally placed glass plate, a 1 mm thick spacer with an internal dimension of 60 mm × 100 mm was placed, and the active energy ray-curable pressure-sensitive adhesive composition prepared in the Examples and Comparative Examples was filled inside the spacer. Then, a 50 μm thick light-release PET film (Toyobo Co., Ltd., polyester film E7002) was placed on top of the active energy ray-curable pressure-sensitive adhesive composition, and the active energy ray-curable pressure-sensitive adhesive composition was heated at a wavelength of 385 nm and an output of 100 mW / cm.2 The UV LED lamp provides an integrated light output of 3000mJ / cm 2 The adhesive composition was cured by irradiating the adhesive so that the release PET films on both sides were then removed, and the cured product (adhesive layer) was touched and evaluated for curability in three stages. ◯: A cured product that can maintain its shape was obtained, and although tack was observed when the cured product was touched, there was no adhesion of liquid uncured material. Δ: A cured product that can maintain its shape was obtained, and tack was observed when the cured product was touched, but there was still some liquid uncured material adhering to it. ×: Curing was insufficient, a cured product that could not maintain its shape was obtained, and a large amount of liquid residue was observed to adhere.
[0088] <Preparation of adhesive sheets and evaluation of adhesion> The active energy ray-curable adhesive composition prepared in the same manner as above was applied to various plate-shaped substrates (substrates), and the substrates were laminated using a tabletop roll laminator (RSL-382S manufactured by Royal Sovereign) with a light-release separator (silicone-coated PET film) to avoid trapping air bubbles, so that the adhesive layer had a thickness of 5 μm. The substrates were then irradiated with ultraviolet light (apparatus: inverter-type conveyor device ECS-4011GX manufactured by Eye Graphics, metal halide lamp: M04-L41 manufactured by Eye Graphics, ultraviolet irradiance: 700 mW / cm). 2 , Accumulated light intensity: 5000mJ / cm 2 ) was then removed, yielding a pressure-sensitive adhesive sheet consisting of the adhesive layer and substrate. Using the resulting pressure-sensitive adhesive sheet, 100 1 mm squares were created in accordance with JIS K 5600, and cellophane tape was attached to each square. The tape was then peeled off in one go, and the number of squares with the adhesive layer remaining on the substrate side was counted, and the adhesion was evaluated according to the following criteria. ◎: No peeling with 100 pieces. 〇: 95 to 99 pieces, no peeling. △: 70 to 94 pieces, no peeling. ×: 0 to 69 pieces, no peeling.
[0089] <Adhesion strength evaluation> The adhesive layer was transferred to various film or plate-shaped substrates under conditions of 23°C and 50% relative humidity, and then pressure-attached by rolling a 2 kg pressure roller back and forth twice. The adhesive was then left for 30 minutes under the same atmosphere. The 180° peel strength (N / 25 mm) was then measured at a peel rate of 300 mm / min using a tensile tester (Tensilon RTA-100, manufactured by ORIENTEC) in accordance with JIS Z0237. ◎:30(N / 25mm) or more ○: 15 (N / 25mm) or more, less than 30 (N / 25mm) △: 8 (N / 25mm) or more, less than 15 (N / 25mm) ×: Less than 8 (N / 25mm)
[0090] <Evaluation of adhesive layer transparency> The total light transmittance of the glass substrate was measured using a haze meter (NDH-2000, manufactured by Nippon Denshoku Industries Co., Ltd.) in accordance with JIS K 7105. The adhesive layer was transferred to a glass substrate under conditions of a temperature of 23°C and a relative humidity of 50%, and the total light transmittance of the glass substrate and adhesive layer was measured. The transmittance of the glass plate was then subtracted to calculate the transmittance of the adhesive layer itself, and the transparency was evaluated into four levels as shown below. ◎: Transmittance is 90% or more ○: Transmittance is 85% or more and less than 90% △: Transmittance is 50% or more and less than 85% ×: Transmittance is less than 50%
[0091] <Contamination resistance (reworkability) evaluation> An adhesive sheet was prepared in the same manner as in the measurement of adhesive strength described above, and after leaving it at 80°C for 24 hours, the surface of the base film was visually inspected for contamination (remaining adhesive layer (glue)) after peeling off the adhesive layer. ◎: No contamination (no adhesive residue). ○: There is very little contamination. △: Slight contamination. ×: Contamination occurs (glue remains).
[0092] <Yellowing resistance evaluation> An adhesive sheet was prepared in the same manner as in the measurement of adhesive strength described above, and set in a xenon fade meter (SC-700-WA: manufactured by Suga Test Instruments Co., Ltd.). 2 After 120 hours of irradiation with ultraviolet light of an intensity of 10 ... ⊚: No yellowing was observed visually. ○: Yellowing is very slight and visible. △: Yellowing can be visually confirmed. ×: Obvious yellowing is visible.
[0093] <Durability evaluation> An adhesive sheet was prepared in the same manner as in the measurement of adhesive strength described above, and after holding it for 100 hours under conditions of a temperature of 85°C and a relative humidity of 85%, the adhesive layer was visually observed and evaluated for any lifting, peeling, bubbles, or cloudiness. ◎: Transparent, no floating, peeling or bubbles. ○: There is a slight cloudiness, but no lifting, peeling, or bubbles. △: Slight cloudiness, lifting, peeling, or bubbles. ×: Severe cloudiness, lifting, peeling, or bubbles.
[0094] As is clear from the results in Table 5, the active energy ray-curable pressure-sensitive adhesive compositions of the Examples had high curability, and the adhesive layers obtained by curing them were highly transparent and had good adhesion and adhesive strength (adhesive strength) to various materials. In particular, the cured products (adhesive layers) obtained from the active energy ray-curable pressure-sensitive adhesive compositions of the present invention contained a (meth)acrylate (A) having both an amide group and a cyclic substituent as a constituent component, and therefore exhibited good contamination resistance when the cured products were peeled from the substrate, as well as good yellowing resistance and durability. On the other hand, the compositions of the Comparative Examples exhibited poor curability, transparency, and adhesion and adhesive strength to various materials, and the cured products also exhibited poor contamination resistance, yellowing resistance, and durability. Furthermore, the combined use of a crosslinking reaction resulted in high adhesive strength between the resulting adhesive layers and various substrates. The compositions and cured products of the Comparative Examples did not exhibit such good properties.
[0095] <Preparation and Evaluation of Adhesive Compositions> Examples 36 to 41 and Comparative Examples 13 and 14 The active energy ray-curable composition obtained in Table 2, (meth)acrylate (A), polymerizable compound (B), photopolymerization initiator (C), and other components were weighed out in the proportions shown in Table 6 and mixed uniformly at room temperature to prepare adhesive compositions for the Examples and Comparative Examples. Using the adhesive compositions, plate-like substrates of the same or different types were bonded together by the following method to prepare adhesive test pieces, and the adhesive strength and impact resistance were evaluated. The results are shown in Table 6.
[0096] Two identical or different plate-shaped substrates measuring 100 mm long x 25 mm wide x 1 mm thick were used, and an adhesive composition was uniformly applied to one of the substrates. When the adhesive composition contained a solvent, a larger amount of the mixture was applied so that the thickness after drying would be approximately the same as when the solvent was not used, and the mixture was dried at 90°C for 2 minutes. Then, in accordance with JIS K 6850, the other plate-shaped substrate was placed on the applied adhesive composition and bonded together so that the overlapping area was 12.5 mm long x 25 mm wide. A spacer was used to adjust the thickness of the adhesive layer to 100 μm, and a bonded test specimen was prepared. Then, UV (ultraviolet irradiator: Inverter-type conveyor device ECS-4011GX manufactured by Eye Graphics, metal halide lamp: M04-L41 manufactured by Eye Graphics, UV irradiance: 700 mW / cm) was applied from the top surface of the bonded transparent or translucent substrates. 2 , Accumulated light intensity: 5000mJ / cm 2 ) or EB (EB irradiation device: Curetron EBC-200-AA3 manufactured by Nissin High Voltage Corporation, accelerating voltage: 200 kV, exposure dose: 20 kGy). In Examples where the curing method in Table 6 is described as UV or EB, the test pieces were irradiated with UV rays or EB rays, respectively, and then used as adhesive test pieces. In Examples where the curing method is described as UV heat, the test pieces were irradiated with UV rays and then further heated at 80°C for 48 hours, and the resulting test pieces were used as adhesive test pieces.
[0097] <Adhesion strength evaluation> Using the obtained adhesive test pieces, the tensile shear strength was measured at a tensile speed of 10 mm / min using a Tensilon RTA-100 tester (manufactured by ORIENTEC Co., Ltd.) in accordance with JIS K 6850. Note that the higher the tensile shear strength, the higher the adhesive strength. ◎: Tensile shear strength is 20 MPa or more. ◯: The tensile shear strength is 15 MPa or more and less than 20 MPa. △: The tensile shear strength is 10 MPa or more and less than 15 MPa. ×: The tensile shear strength is less than 10 MPa.
[0098] <Impact resistance evaluation> Using the adhesive test pieces obtained in the same manner as above, the impact peel adhesive strength was measured in accordance with JIS K 6855 using an impact tester No. 511 (manufactured by Mize Testing Instruments Co., Ltd.) Note that the higher the impact peel adhesive strength, the higher the impact resistance. ◎: Impact peel adhesive strength is 20KJ / m2 or more. ○: Impact peel adhesive strength is 15 KJ / m2 or more and less than 20 KJ / m2. △: Impact peel adhesive strength is 10KJ / m2 or more and less than 15KJ / m2. ×: Impact peel adhesive strength is less than 10 KJ / m2.
[0099] As is clear from the results in Table 6, the active energy ray-curable adhesive compositions of the examples were easily cured with either ultraviolet (UV) or electron beam (EB) radiation, resulting in laminates with adhesive layers having high adhesive strength and impact resistance. Further heating after UV or EB irradiation allowed for continued thermal curing, making the adhesive suitable for bonding opaque substrates and dissimilar materials. In particular, when the cyclic substituent of the (meth)acrylate (A) has an unsaturated bond, photopolymerization by active energy rays proceeds rapidly, leaving the unsaturated bond of the cyclic substituent more likely to remain. Subsequent thermal polymerization allowed the unsaturated bond of the cyclic substituent to be completely polymerized, further improving adhesive strength and impact resistance. The compositions and cured products of the comparative examples did not exhibit such favorable properties.
[0100] <Preparation and evaluation of coating compositions> Examples 42 to 47 and Comparative Examples 15 and 16 The active energy ray-curable composition obtained in Table 2, (meth)acrylate (A), polymerizable compound (B), photopolymerization initiator (C), and other components were weighed in the proportions shown in Table 7 and mixed uniformly at room temperature to prepare coating compositions of Examples and Comparative Examples. The coating compositions were applied to various substrates, and the wettability of the coating compositions to the various substrates was evaluated. In addition, the coating compositions were applied to ABS plates and cured with UV, EB, or UV and then EB to evaluate the curability of the coating compositions, and the abrasion resistance of the resulting cured coating films was evaluated. The results are shown in Table 7.
[0101] <Wettability evaluation> The resulting coating compositions were applied to various substrates using a bar coater (RDS 3), and the degree of repelling of the coating film was visually observed, and the wettability was evaluated according to the following four levels. ◎: No repelling and uniform coating film. ◯: There is very little repelling, but the coating is almost uniform. △: There is some repelling, but the coating is generally uniform overall. ×: There is a lot of repelling and the coating film is uneven.
[0102] <Appearance evaluation of cured coating film> The resulting coating compositions were applied to a 3 mm thick ABS resin plate using a bar coater (RDS 6) so that the cured film thickness was 25 μm. The resin plate was then irradiated with UV (ultraviolet irradiator: Inverter type conveyor device ECS-4011GX manufactured by Eye Graphics, metal halide lamp: M04-L41 manufactured by Eye Graphics, UV irradiance: 700 mW / cm). 2 , Accumulated light intensity: 2000mJ / cm 2) or EB (EB irradiation device: Curetron EBC-200-AA3 manufactured by Nissin High Voltage Co., Ltd., acceleration voltage: 200 kV, exposure dose: 20 kGy). In Table 7, examples where the curing method is described as "UV then EB" were irradiated with UV rays and then with EB rays. The cured coating films obtained were touched with a finger to check the state of adhesion of the coating composition to the finger, and curability was evaluated. The surface smoothness and transparency of the cured coating films were also evaluated by visual observation. The results of these evaluations are shown in Table 7. In the appearance evaluation, when a pigment was contained, only the surface smoothness of the cured coating film was evaluated. Curability: ◯: The coating composition no longer adheres. Δ: A small amount of the coating composition was adhered. ×: Coating composition adhered Coating appearance: ⊚: The surface was smooth and the coating film was transparent. ◯: The surface was smooth and the coating film was transparent overall with slight cloudy areas. Δ: The surface was uneven or the coating film had cloudy areas. ×: The surface was uneven and the coating film was cloudy.
[0103] <Wear resistance evaluation> The resulting cured coating film was evaluated for abrasion resistance in accordance with ISO 20566 using a car wash abrasion tester (Amtec laboratory Car Wash device, manufactured by Amtec Kistler GmbH). The 20° gloss of the cured coating film before and after the abrasion test was measured using a BYK Gardner gloss meter, and the gloss retention was calculated using the following formula. The abrasion resistance of the coating film was evaluated according to the following criteria. The higher the gloss retention, the higher the abrasion resistance of the cured coating film. Gloss retention rate (%) = (gloss value after rubbing) / (gloss value before rubbing) x 100% Regarding the calculated gross retention rate, ○: Gross retention rate 80% or more △: Gross retention rate 60% or more but less than 80% ×: Gloss retention rate less than 60%
[0104] As is clear from the results in Table 7, the active energy ray-curable coating compositions of the Examples had good wettability to various substrates, excellent curability, and the resulting cured coating films had good appearance and abrasion resistance. On the other hand, the coating compositions of the Comparative Examples had poor curability, and the resulting cured films had poor appearance and abrasion resistance. The coating composition of the present invention has good wettability to a wide range of substrates, from general-purpose plastics to wood and metal, high curability to active energy rays, and the resulting cured coating films have good properties, making it suitable for a wide range of uses, such as coatings for various electronic components, indoor and outdoor paints, floor paints, and vehicle paints.
[0105] <Preparation and Evaluation of Active Energy Ray-Curable Sealant Composition> Examples 48 to 52 and Comparative Examples 17 and 18 The active energy ray-curable composition obtained in Table 2, (meth)acrylate (A), polymerizable compound (B), photopolymerization initiator (C), and other components were weighed out in the proportions shown in Table 8 and mixed uniformly at room temperature to prepare sealant compositions of Examples and Comparative Examples. Using the obtained sealant compositions, sealants (sealant cured products) were produced by the following methods, and their physical properties were evaluated.
[0106] <Preparation of cured sealant> A silicone spacer (30 mm long x 15 mm wide x 3 mm thick) was placed on a glass plate (50 mm long x 50 mm wide x 5 mm thick), and copper foil (5 mm long x 50 mm wide x 80 μm thick) was placed inside the spacer, and the prepared active energy ray-curable sealant composition was poured into it. After sufficient degassing, the spacer was irradiated with ultraviolet light (apparatus: Inverter-type conveyor device ECS-4011GX manufactured by Eye Graphics, metal halide lamp: M04-L41 manufactured by Eye Graphics, ultraviolet irradiance: 700 mW / cm 2 , Accumulated light intensity: 1000mJ / cm 2 The properties of the resulting cured product were evaluated by the following methods, and the results are shown in Table 8.
[0107] <Transparency evaluation of cured sealant> The obtained cured sealant product was left to stand for 24 hours in an atmosphere of 23°C and 50% relative humidity, and then the transmittance of the cured product was measured using a haze meter (NDH-2000, manufactured by Nippon Denshoku Industries Co., Ltd.) and the transparency was evaluated into four levels as shown below. ◎: Transmittance is 90% or more ○: Transmittance is 85% or more and less than 90% △: Transmittance is 50% or more and less than 85% ×: Transmittance is less than 50%
[0108] <Evaluation of humidity and heat yellowing resistance> The resulting cured sealant was left to stand for 24 hours in an atmosphere at 23°C and 50% relative humidity, after which the transmission spectrum of the cured product was measured using a dedicated transmission color measuring instrument (TZ-6000, manufactured by Nippon Denshoku Industries Co., Ltd.) and recorded as the initial b value. The cured product was then placed in a thermo-hygrostat set at 85°C and 85% relative humidity for 500 hours to conduct an accelerated test of moist heat yellowing resistance. After the test, the cured product was also left to stand for 24 hours in an atmosphere at 23°C and 50% relative humidity, and the transmission color was measured and recorded as the post-moist heat b value. The difference between the post-moist heat b value and the initial b value was recorded as the change Δb (Δb = post-moist heat b value - initial b value). The moist heat yellowing resistance of the cured product was evaluated using the following four-point scale. ⊚: Both the initial b value and the b value after moist heat are 0.2 or less, and Δb is 0.1 or less. ◯: Either one or both of the initial b value and the b value after wet heat treatment exceeds 0.2, but both are 0.5 or less, and Δb is 0.2 or less. Δ: Either one or both of the initial b value and the b value after moist heat treatment exceeds 0.5, but both are 1.0 or less, and Δb is 0.3 or less. ×: Either or both of the initial b value and the b value after wet heat treatment exceed 1.0, or Δb exceeds 0.3.
[0109] <Water resistance evaluation of cured sealant> A 1g specimen was cut from the resulting cured product and placed in a thermo-hygrostat at 85°C and 95% relative humidity. After leaving the specimen standing for 48 hours, the weight of the specimen was measured again, and the water absorption was calculated using the formula below. The water resistance was evaluated into four levels as shown below. The lower the water absorption, the higher the water resistance of the cured product. The lower the water absorption, the higher the water resistance. Water absorption rate (%) = (weight after water absorption - weight before water absorption) / weight before water absorption × 100% ◎: Water absorption rate is less than 1.0% ○: Water absorption rate is 1.0% or more and less than 2.0% △: Water absorption rate is 2.0% or more and less than 3.0% ×: Water absorption rate is 3.0% or more
[0110] <Outgassing resistance evaluation> A 1g specimen was cut from the resulting cured product and placed in a thermostatic chamber set at 100°C as a test piece. A dry nitrogen stream was passed through the specimen for 24 hours, after which the specimen was weighed again and the outgassing rate was calculated using the following formula and rated into four levels. The lower the outgassing rate, the higher the outgassing resistance. Outgassing rate (%) = (weight after test - weight before test) / weight before test x 100% ◎: Incidence rate is less than 0.1% ○: The incidence rate is 0.1% or more and less than 0.3% △: Incidence rate is 0.3% or more and less than 1.0% ×: incidence rate is 1.0% or more
[0111] <Heat cycle resistance evaluation> The resulting cured product was subjected to a cycle of leaving it at -40°C for 30 minutes and then at 100°C for 30 minutes, which was repeated 100 times. The condition of the cured product was visually observed and the heat cycle resistance was evaluated into four stages. ◎: No change was observed. ◯: A few bubbles are observed, but no cracks are observed. Transparent. △: Some bubbles or cracks were observed, and the film was slightly cloudy. ×: Bubbles or cracks occur all over the surface, and the surface is semi-transparent.
[0112] <Corrosion resistance evaluation> After the above-mentioned moist heat yellowing resistance test, the surface of the copper foil was visually observed and the corrosion resistance of the cured product was evaluated into four stages. ◎: No corrosion ○: Slight corrosion △: Slight corrosion ×: Severe corrosion Corrosion resistance was evaluated and the results are shown in Table 5.
[0113] As is clear from the results in Table 8, the sealant cured products obtained from the active energy ray-curable sealant compositions of the Examples had high transparency and water resistance, generated little outgassing, and had good resistance to moist heat yellowing and metal corrosion (corrosion resistance). On the other hand, these physical properties were not observed in the cured products obtained from the curable compositions of the Comparative Examples. The sealant composition of the present invention can be suitably used as a sealant for optical elements, electrical devices, etc.
[0114] <Preparation and Evaluation of Active Energy Ray-Curable Nail Cosmetics> Examples 53 to 58 and Comparative Examples 19 and 20 The active energy ray-curable composition obtained in Table 2, (meth)acrylate (A), polymerizable compound (B), photopolymerization initiator (C), and other components were weighed out in the proportions shown in Table 9 and mixed uniformly at room temperature to prepare nail cosmetics of Examples and Comparative Examples. Using the obtained nail cosmetics, the curability and the physical properties of the obtained cured films were evaluated by the following methods.
[0115] <Evaluation of the hardening properties of nail cosmetics> The active energy ray-curable nail cosmetics prepared in the examples and comparative examples were applied to a nylon 6 test piece ("SHT-N6(NC)" manufactured by Toray Plastics Precision Co., Ltd.) using a bar coater to a film thickness of 10 μm, and then irradiated with ultraviolet light using a UV LED lamp designed specifically for gel nails (manufactured by Beauty Nailer, wavelength 405 nm, 48 W). The time it took for the tackiness to disappear when touching the surface of the cured film was evaluated into four levels. The shorter the time required for the tackiness to disappear, the higher the curability. ◎: The tack disappears in less than 1 minute. ○: The tack disappears in 1 minute or more but less than 3 minutes. △: The tack disappears in 3 minutes or more but less than 10 minutes. ×: The tack does not disappear even after 10 minutes or more.
[0116] <Adhesion (nylon substrate) evaluation> The photocurable nail cosmetics obtained in each of the Examples and Comparative Examples were applied to nylon 6 test pieces in the same manner as above, and cured films were produced by irradiating with light for 3 minutes. Using the obtained cured films, 100 1 mm square grids were made with a cutter knife in accordance with JIS K 5600, and the number of grids remaining on the test pieces when commercially available cellophane tape was attached and then peeled off was evaluated into four levels. The more grids remaining on the test pieces, the higher the adhesion. ◎: The number of remaining squares is 100. ○: The number of remaining grids is 90 to 99. △: The number of remaining grids is 60 to 89. ×: The number of remaining squares is less than 60.
[0117] <Evaluation of surface hardness of cured film> In the same manner as in the adhesion evaluation, cured films of each Example and Comparative Example were prepared, and the surface of the obtained film was scratched with a pencil having a hardness of HB under a load of 750 g. The presence or absence of peeling and scratches was visually confirmed and rated into three levels. The fewer scratches and peeling occurred, the higher the surface hardness. ◯: No scratches or peeling occurred. The surface hardness was pencil hardness HB or higher. △: No peeling occurred, but scratches occurred. ×: Peeling occurred.
[0118] <Surface gloss evaluation> In the same manner as in the adhesion evaluation, cured films were prepared for each of the examples and comparative examples, and the gloss of the film surface was visually observed and rated on a three-level scale. ○: Shiny. △: Light reflection can be seen, but there is some cloudiness. ×: No light reflection was observed and there was no gloss.
[0119] As is clear from the results in Table 9, the active energy ray-curable nail cosmetics of the Examples exhibited excellent curability compared to commercially available UV lamps specifically designed for gel nails, while also exhibiting high adhesion to nylon substrates (materials containing numerous amide groups, similar to nails, whose main component is protein). These results demonstrate that the active energy ray-curable nail cosmetics of the present invention can be suitably used as a gel nail base gel to be applied directly to nails. Furthermore, the surface hardness and gloss of the resulting cured film were good, making them suitable for use as a top coat for gel nails. On the other hand, the curable compositions of the Comparative Examples exhibited poor curability, and the surface hardness and gloss of the cured film were low.
[0120] <Preparation and Evaluation of Active Energy Ray-Curable Decorative Coating Agents> Examples 59 to 63 and Comparative Examples 21 and 22 The active energy ray-curable composition obtained in Table 2, (meth)acrylate (A), polymerizable compound (B), photopolymerization initiator (C), and other components were weighed out in the proportions shown in Table 10 and mixed uniformly at room temperature to prepare decorative coating agents (active energy ray-curable compositions used for decorative molding and decorative processing of decorative films, decorative sheets, etc.) of Examples and Comparative Examples. Using the obtained decorative coating agents, laminates were produced by the following decorative processing, and the physical properties of the obtained laminates were evaluated.
[0121] <Preparation of laminate> The resulting decorative coating agent was applied to a 180 μm thick PC film ("Panlite PC-2151" manufactured by Teijin Ltd.) using a bar coater (RDS 6) so that the film thickness after drying would be 5 μm. The coating was then heated at 80°C for 3 minutes and irradiated with ultraviolet light (high-pressure mercury lamp 300 mW / cm 2 , 1,000mJ / cm 2) to cure the coating, thereby obtaining a laminate having a hard coating layer. The obtained laminate was cut out, and the surface tack resistance, elongation, pencil hardness, scratch resistance, bending resistance, and sunscreen agent resistance of the hard coating layer were evaluated by the methods described below, and the results are shown in Table 10. In Examples 57 and 60, the laminate after curing with active energy rays was placed in an incubator at 80°C and heat-treated for 8 hours, after which various physical properties were evaluated.
[0122] <Surface tack resistance evaluation> The surface of the film of the obtained laminate was touched with a finger to evaluate the stickiness. ◎: No stickiness at all. Good: There is some stickiness, but finger marks do not remain on the surface. △: Sticky and leaves finger marks on the surface. ×: Extremely sticky, fingers stick to the surface.
[0123] <Growth rate evaluation> The resulting laminate was cut to a length of 50 mm and a width of 15 mm, and fixed to a Tensilon universal testing machine RTA-100 (manufactured by Orientec Co., Ltd.) with a chuck distance of 25 mm. The specimen was stretched in one direction at a rate of 250 mm / min in an oven set to a temperature of 150°C while visually observing the appearance, and the length (mm) of the specimen was measured when cracks or whitening occurred in the coating layer. The elongation was calculated and evaluated using the following method. Elongation (%) = (length of specimen after test / 25) x 100% ◎: Elongation rate is 200% or more ○: Elongation rate is 150% or more but less than 200% △: Elongation rate is 110% or more but less than 150% ×: Elongation rate is less than 110%
[0124] <Surface hardness evaluation> Using a test piece of the laminate, a pencil was used to scratch the surface of the laminate for approximately 10 mm at a 45° angle in accordance with JIS K 5600. The pencil hardness of the hardest pencil that did not scratch the surface of the laminate was taken as the pencil hardness, and the surface hardness was evaluated as follows. ◎: Pencil hardness is 2H or more ○: Pencil hardness is HB to H △:Pencil hardness is 3B~B ×: Pencil hardness is 4B or less
[0125] <Scratch resistance evaluation> A test piece of the laminate was reciprocated 10 times with #0000 steel wool at a weight of 200 g, and the surface of the laminate was visually observed to evaluate scratch resistance. ⊚: No peeling or damage to the film was observed. ○: Slight fine scratches are observed in part of the film. △: Streak-like scratches are observed throughout the membrane. ×: Peeling of the film occurs.
[0126] <Bending resistance evaluation> A test piece of the laminate was bent 180° so that the coated surface was on the outside, a 1 kg weight was placed on it and left for 10 minutes, and the presence or absence of cracks on the surface of the laminate was visually observed to evaluate the bending resistance. ⊚: No cracks were observed. ○: The folded portion was partially whitened. △: Partial cracking was observed at the bent portion. ×: Cracks were observed at the bent portion.
[0127] <Sunscreen resistance evaluation> The sunscreen UltraSheer DRY-TOUCH SUNSCREEN SPF100+ (manufactured by Johnson & Johnson) was applied to the coated surface of the laminate test piece to a diameter of approximately 1 cm, heated at 80°C for 6 hours, allowed to cool, and then washed off with a neutral detergent. The surface condition was observed, and sunscreen resistance was evaluated as follows. ◎: No traces of sunscreen were found. ○: A slight transparent mark is visible in the area where the sunscreen was applied. △: White marks remain where the sunscreen was applied, and the surface is swollen. ×: The area where the sunscreen was applied was sticky and the surface was peeling.
[0128] As is clear from the results in Table 10, a laminate having a decorative coating layer (decorative coating film) could be easily obtained by applying the active energy ray-curable decorative coating agent of the example to the surface of a general-purpose plastic substrate and curing it with active energy ray. The surface (coated surface) of the obtained laminate had tack resistance, high hardness, and excellent scratch resistance and sunscreen resistance. The resulting laminate also had good elongation and bending resistance. In particular, after active energy ray curing, further heat treatment relieves stress between the coated surface and the substrate. Furthermore, when the cyclic substituent of the (meth)acrylate (A), an essential component of the decorative coating agent, contains an unsaturated bond, thermal polymerization of the unsaturated bond proceeds during the heat treatment process, further improving the surface (coated surface) hardness, scratch resistance, and sunscreen resistance. On the other hand, the curable composition of the comparative example did not exhibit similar decorative performance. The decorative coating agent of the present invention is suitable for a wide variety of decorative molding, decorative processing, and decorative printing applications, including decorative films, decorative sheets, and decorative coatings.
[0129] <Preparation and evaluation of active energy ray-curable dental materials> Examples 64 to 68 and Comparative Examples 23 and 24 The active energy ray-curable composition, (meth)acrylate (A), polymerizable compound (B), photopolymerization initiator (C), and other components shown in Table 2 were weighed and uniformly mixed at room temperature to prepare an active energy ray-curable dental material. The solubility or dispersibility of the dental material (when an insoluble inorganic filler, pigment, or the like was blended) was visually observed, and storage stability was evaluated. The results are shown in Table 11. Furthermore, a cured dental material was prepared using the dental material by the following method, and the curability of the dental material, as well as the surface smoothness, hardness, and adhesive strength of the resulting cured dental material were evaluated. The results are shown in Table 11. For Examples 62 and 65, the cured dental material after active energy ray curing was placed in an incubator at 80°C and heated for 8 hours, after which various physical properties were evaluated.
[0130] <Solubility (dispersibility) evaluation> ⊚: The composition obtained was homogeneous and transparent. ◯: The resulting composition was homogeneous and translucent. Δ: The obtained composition was cloudy and it was difficult to judge its uniformity. ×: The resulting composition was not completely mixed.
[0131] <Storage stability evaluation> The obtained compositions of the Examples and Comparative Examples were placed in light-shielding screw tubes, the lids were closed, and the tubes were stored under two conditions: at 40°C for 1 month and at 80°C for 2 weeks. The state of dissolution or dispersion of the compositions after storage was checked to evaluate their storage stability. ○: No change in state was observed after storage under both conditions of 40°C for one month and 80°C for two weeks. △: A change in state was observed after storage under either one of the conditions of 40°C for one month or 80°C for two weeks. ×: Changes in state were observed after storage under both conditions: 1 month at 40°C and 2 weeks at 80°C.
[0132] <Curing evaluation> The obtained compositions of the Examples and Comparative Examples were filled into a polytetrafluoroethylene mold (20 mm × 20 mm × 10 mm) with a hole of 6 mm diameter in the center, and the mold was pressed with a polypropylene film. The mold was then placed in a dental light irradiator (Tokuso Power Light, manufactured by Tokuyama Dental Co., Ltd., light output density 700 mW / cm). 2 , light intensity at the irradiation surface 640-650mW / cm 2 The light source was a halogen lamp with an 8mm aperture and was placed in close contact with the polypropylene film and irradiated for 30 seconds. The polypropylene film was then peeled off and the cured product was touched with the hand to check for stickiness and the presence or absence of uncured components. ◎: No stickiness at all (completely cured). ○: There is some stickiness, but no finger marks remain on the surface (almost completely cured, no need to wipe off uncured components). △: Sticky and finger marks remain on the surface (incomplete curing, uncured components need to be wiped off). ×: Extremely sticky, fingers stick to the surface (a large amount of uncured components remain, and the film cannot be used as a cured film).
[0133] <Surface smoothness> The surface of the cured product obtained in the curability evaluation was visually observed to check the smoothness and gloss, and the surface smoothness was evaluated. ◎: The surface is smooth and glossy. ○: The surface is almost smooth, with slight cloudiness or slight irregularities. △: The surface is cloudy overall, and some irregularities and granularity are observed. ×: The surface is entirely cloudy and covered with granular particles.
[0134] <Hardness evaluation> The surface of the cured product obtained in the curability evaluation was buffed, and the Knoop hardness was measured using a Matsuzawa Seiki microhardness tester under a load of 10 g for 20 seconds at a temperature of 23°C. ◎: Knoop hardness is 200KHN or more (equivalent to permanent tooth enamel). ○: Knoop hardness is 70KHN or more and less than 200KHN (equivalent to dentin). △: Knoop hardness is less than 70KHN. ×: Not cured, so measurement was not possible.
[0135] <Adhesion strength (dentin adhesion strength)> A bovine mandibular anterior tooth was polished with #1000 waterproof abrasive paper under running water to remove a flat dentin surface for bonding. The surface was then dried by blowing compressed air for 10 seconds, and a tape with a 3 mm diameter hole was attached to set the adhesion surface. Subsequently, an adhesion test piece was prepared by a known method (see the method described in JP 2010-208964 A). The adhesion test piece was immersed in 37°C water for 24 hours, and then the tensile bond strength was measured using an Instron universal testing machine (crosshead speed 2 mm / min), and this was taken as the adhesive strength of the composition obtained in the examples and comparative examples to enamel and dentin. The tensile bond strength value was the average value of five test pieces. ◎: The bond strength between enamel and dentin is 20 MPa or more. ○: The bond strength between enamel and dentin is 20 MPa or more at least in one case. △: The bond strength between enamel and dentin is 7 MPa or more. ×: The bond strength between enamel and dentin is less than 7 MPa.
[0136] As is clear from the results in Table 11, the active energy ray-curable dental materials of the Examples have high solubility (or dispersibility), curability, and storage stability, and the cured products obtained by curing them have good hardness, surface smoothness, and adhesive strength. On the other hand, the compositions of the Comparative Examples have low solubility, curability, and storage stability, and do not cure sufficiently, so the hardness and surface smoothness of the obtained cured products are low and the adhesive strength is insufficient.
[0137] As shown by the evaluation results of the above-mentioned examples and comparative examples, the active energy ray-curable composition containing a (meth)acrylate (A) having a specific structure and a polymerizable compound (B) according to the present invention has high transparency and good curability due to the cyclic substituent of A and the amide, while also having good wettability and adhesion to various substrates. Furthermore, the cured products obtained by curing them have excellent water resistance, heat resistance, impact resistance, abrasion resistance, etc. Due to the interaction between the (meth)acrylate (A) and the polymerizable compound (B), the curing shrinkage that occurs during curing of the curable composition is low, and the resulting cured products have no internal stress or distortion, resulting in good durability. On the other hand, it is clear that the above-mentioned various physical properties cannot be obtained with a curable composition and its cured product that does not contain the (meth)acrylate (A) or the polymerizable compound (B). In other words, it was confirmed that the various physical properties of the active energy ray-curable composition of the present invention and the cured products obtained therefrom are due to the interaction between the (meth)acrylate (A) and the polymerizable compound (B) contained therein.
[0138] [Table 1]
[0139] [Table 2]
[0140] [Table 3]
[0141] [Table 4]
[0142] [Table 5]
[0143] [Table 6]
[0144] [Table 7]
[0145] [Table 8]
[0146] [Table 9]
[0147] [Table 10]
[0148] [Table 11] [Industrial Applicability]
[0149] As described above, the active energy ray-curable composition of the present invention contains a specific (meth)acrylate (A) and a polymerizable compound (b1) having a chain substituent and / or a polymerizable compound (b2) having a cyclic substituent, and thereby has high transparency and good curability, while also exhibiting excellent wettability to various substrates having a wide range of polarities from low to high, and can produce cured products with low cure shrinkage and excellent water resistance, impact resistance, abrasion resistance, and durability. The curable composition can be used in active energy ray-curable ink compositions, ink compositions for two-dimensional or three-dimensional modeling, pressure-sensitive adhesive compositions, adhesive compositions, paint compositions, sealant compositions, nail cosmetics, decorative coating agents, dental materials, and the like.
Claims
1. (A) a (meth)acrylate having an amide group and a cyclic substituent in the molecule; An active energy ray-curable composition containing a polymerizable compound (B) (excluding A) having one or more (meth)acrylamide groups and / or (meth)acrylate groups in the molecule, The polymerizable compound (B) contains a polymerizable compound (b1) having a chain substituent having 1 to 36 carbon atoms and a polymerizable compound (b2) having a cyclic substituent having 3 to 20 carbon atoms, An active energy ray-curable composition, wherein the content of (A) is 0.1 to 99.5 mass%, the content of (b1) is 0.3 to 80 mass%, and the content of (b2) is 0.2 to 70 mass%, based on the entire active energy ray-curable composition.
2. 2. The active energy ray-curable composition according to claim 1, wherein the (meth)acrylate (A) has, as a cyclic substituent, one or more substituents selected from a saturated or unsaturated polycyclic aliphatic ring, a monocyclic or polycyclic aromatic ring, a saturated or unsaturated aliphatic heterocycle, and an aromatic heterocycle.
3. The active energy ray-curable composition according to claim 1 or 2, wherein the (meth)acrylate (A) has an amide group between the (meth)acrylate group and the cyclic substituent.
4. The active energy ray-curable composition according to any one of claims 1 to 3, wherein the (meth)acrylate (A) has a cyclic substituent which is an unsaturated ring or the cyclic substituent further has an unsaturated substituent.
5. The active energy ray-curable composition according to any one of claims 1 to 4, wherein the mass ratio of the contents of the polymerizable compounds (b1) and (b2) is 30 / 1 to 1 / 10.
6. The active energy ray-curable composition according to any one of claims 1 to 5, which has a cure shrinkage rate of 5% or less.
7. The active energy ray-curable composition according to any one of claims 1 to 6, wherein a cured product of the active energy ray-curable composition has a saturated water absorption of 10% or less.
8. An ink composition comprising the active energy ray-curable composition according to any one of claims 1 to 7.
9. An ink composition for two-dimensional or three-dimensional modeling, comprising the active energy ray-curable composition according to any one of claims 1 to 7.
10. A pressure-sensitive adhesive composition comprising the active energy ray-curable composition according to any one of claims 1 to 7.
11. An adhesive composition comprising the active energy ray-curable composition according to any one of claims 1 to 7.
12. A coating composition comprising the active energy ray-curable composition according to any one of claims 1 to 7.
13. A sealant composition comprising the active energy ray-curable composition according to any one of claims 1 to 7.
14. A nail cosmetic comprising the active energy ray-curable composition according to any one of claims 1 to 7.
15. A decorative coating agent comprising the active energy ray-curable composition according to any one of claims 1 to 7.
16. A dental material comprising the active energy ray-curable composition according to any one of claims 1 to 7.
Citation Information
Patent Citations
Polycyclic carboxamide with (METH)acryloyl group
JP2018095626A
Active energy ray-curable composition and cured product
JP2021123720A
Method for producing novel alicyclic ester compound, novel alicyclic ester compound, (METH)acrylic copolymer produced by polymerizing said compound, and photosensitive resin composition using said copolymer
WO2015122470A1
Surface treatment agent
WO2019163570A1